A flexible toolchain for symbolic rabin games under fair and stochastic uncertainties - Majumdar, Rupak; Mallik, Kaushik; Rychlicki, Mateusz; Schmuck, Anne-Kathrin; Soudjani, Sadegh
This resource contains the artifacts for reproducing the experimental results presented in the paper titled "A Flexible Toolchain for Symbolic Rabin Games under Fair and Stochastic Uncertainties" that has been submitted in CAV 2023.

Compositional policy learning in stochastic control systems with formal guarantees - Zikelic, Dorde; Lechner, Mathias; Verma, Abhinav; Chatterjee, Krishnendu; Henzinger, Thomas A (37th Conference on Neural Information Processing Systems)
Reinforcement learning has shown promising results in learning neural network policies for complicated control tasks. However, the lack of formal guarantees about the behavior of such policies remains an impediment to their deployment. We propose a novel method for learning a composition of neural network policies in stochastic environments, along with a formal certificate which guarantees that a specification over the policy's behavior is satisfied with the desired probability. Unlike prior work on verifiable RL, our approach leverages the compositional nature of logical specifications provided in SpectRL, to learn over graphs of probabilistic reach-avoid specifications. The formal guarantees are provided by learning neural network policies together with reach-avoid supermartingales (RASM) for the graph’s sub-tasks and then composing them into a global policy. We also derive a tighter lower bound compared to previous work on the probability of reach-avoidance implied by a RASM, which is required to find a compositional policy with an acceptable probabilistic threshold for complex tasks with multiple edge policies. We implement a prototype of our approach and evaluate it on a Stochastic Nine Rooms environment.

A framework for grassroots research collaboration in machine learning and global health - Currin, Christopher; Asiedu , Mercy Nyamewaa; Fourie, Chris; Rosman, Benjamin; Turki, Houcemeddine; Lambebo Tonja, Atnafu; Abbott, Jade; Ajala, Marvellous; Adedayo, Sadiq Adewale; Emezue, Chris Chinenye; Machangara, Daphne (1st Workshop on Machine Learning & Global Health)
Traditional top-down approaches for global health have historically failed to achieve social progress (Hoffman et al., 2015; Hoffman & Røttingen, 2015). Recently, however, a more holistic, multi-level approach termed One Health (OH) (Osterhaus et al., 2020) is being adopted. Several sets of challenges have been identified for the implementation of OH (dos S. Ribeiro et al., 2019), including policy and funding, education and training, and multi-actor, multi-domain, and multi-level collaborations. These exist despite the increasing accessibility to knowledge and digital collaborative research tools through the internet. To address some of these challenges, we propose a general framework for grassroots community-based means of participatory research. Additionally, we present a specific roadmap to create a Machine Learning for Global Health community in Africa. The proposed framework aims to enable any small group of individuals with scarce resources to build and sustain an online community within approximately two years. We provide a discussion on the potential impact of the proposed framework for global health research collaborations.

Monitoring hyperproperties with prefix transducers - Chalupa, Marek; Henzinger, Thomas A (23nd International Conference on Runtime Verification)
Hyperproperties are properties that relate multiple execution traces. Previous work on monitoring hyperproperties focused on synchronous hyperproperties, usually specified in HyperLTL. When monitoring synchronous hyperproperties, all traces are assumed to proceed at the same speed. We introduce (multi-trace) prefix transducers and show how to use them for monitoring synchronous as well as, for the first time, asynchronous hyperproperties. Prefix transducers map multiple input traces into one or more output traces by incrementally matching prefixes of the input traces against expressions similar to regular expressions. The prefixes of different traces which are consumed by a single matching step of the monitor may have different lengths. The deterministic and executable nature of prefix transducers makes them more suitable as an intermediate formalism for runtime verification than logical specifications, which tend to be highly non-deterministic, especially in the case of asynchronous hyperproperties. We report on a set of experiments about monitoring asynchronous version of observational determinism.

QuePaxa: Escaping the tyranny of timeouts in consensus - Tennage, Pasindu; Basescu, Cristina; Kokoris Kogias, Eleftherios; Syta, Ewa; Jovanovic, Philipp; Estrada-Galinanes, Vero; Ford, Bryan (Proceedings of the 29th Symposium on Operating Systems Principles)
Leader-based consensus algorithms are fast and efficient under normal conditions, but lack robustness to adverse conditions due to their reliance on timeouts for liveness. We present QuePaxa, the first protocol offering state-of-the-art normal-case efficiency without depending on timeouts. QuePaxa uses a novel randomized asynchronous consensus core to tolerate adverse conditions such as denial-of-service (DoS) attacks, while a one-round-trip fast path preserves the normal-case efficiency of Multi-Paxos or Raft. By allowing simultaneous proposers without destructive interference, and using short hedging delays instead of conservative timeouts to limit redundant effort, QuePaxa permits rapid recovery after leader failure without risking costly view changes due to false timeouts. By treating leader choice and hedging delay as a multi-armed-bandit optimization, QuePaxa achieves responsiveness to prevalent conditions, and can choose the best leader even if the current one has not failed. Experiments with a prototype confirm that QuePaxa achieves normal-case LAN and WAN performance of 584k and 250k cmd/sec in throughput, respectively, comparable to Multi-Paxos. Under conditions such as DoS attacks, misconfigurations, or slow leaders that severely impact existing protocols, we find that QuePaxa remains live with median latency under 380ms in WAN experiments.

Unified treatment of contact, friction and shock-propagation in rigid body animation - Chen, Yi-Lu; Ly, Mickaël; Wojtan, Christopher J (Proceedings of the ACM SIGGRAPH/Eurographics Symposium on Computer Animation)

Monitoring hyperproperties with prefix transducers - Chalupa, Marek; Henzinger, Thomas A
This artifact aims to reproduce experiments from the paper Monitoring Hyperproperties With Prefix Transducers accepted at RV'23, and give further pointers to implementation of prefix transducers. It has two parts: a pre-compiled docker image and sources that one can use to compile (locally or in docker) the software and run the experiments.

Individual and social immunity against viral infections in ants - Franschitz, Anna
Social insects fight disease using their individual immune systems and the cooperative sanitary behaviors of colony members. These social defenses are well explored against externally-infecting pathogens, but little is known about defense strategies against internally-infecting pathogens, such as viruses. Viruses are ubiquitous and in the last decades it has become evident that also many ant species harbor viruses. We present one of the first studies addressing transmission dynamics and collective disease defenses against viruses in ants on a mechanistic level. I successfully established an experimental ant host – viral pathogen system as a model for the defense strategies used by social insects against internal pathogen infections, as outlined in the third chapter. In particular, we studied how garden ants (Lasius neglectus) defend themselves and their colonies against the generalist insect virus CrPV (cricket paralysis virus). We chose microinjections of virus directly into the ants’ hemolymph because it allowed us to use a defined exposure dose. Here we show that this is a good model system, as the virus is replicating and thus infecting the host. The ants mount a clear individual immune response against the viral infection, which is characterized by a specific siRNA pattern, namely siRNAs mapping against the viral genome with a peak of 21 and 22 bp long fragments. The onset of this immune response is consistent with the timeline of viral replication that starts already within two days post injection. The disease manifests in decreased survival over a course of two to three weeks. Regarding group living, we find that infected ants show a strong individual immune response, but that their course of disease is little affected by nestmate presence, as described in chapter four. Hence, we do not find social immunity in the context of viral infections in ants. Nestmates, however, can contract the virus. Using Drosophila S2R+ cells in culture, we showed that 94 % of the nestmates contract active virus within four days of social contact to an infected individual. Virus is transmitted in low doses, thus not causing disease transmission within the colony. While virus can be transmitted during short direct contacts, we also assume transmission from deceased ants and show that the nestmates’ immune system gets activated after contracting a low viral dose. We find considerable potential for indirect transmission via the nest space. Virus is shed to the nest, where it stays viable for one week and is also picked up by other ants. Apart from that, we want to underline the potential of ant poison as antiviral agent. We determined that ant poison successfully inactivates CrPV in vitro. However, we found no evidence for effective poison use to sanitize the nest space. On the other hand, local application of ant poison by oral poison uptake, which is part of the ants prophylactic behavioral repertoire, probably contributes to keeping the gut of each individual sanitized. We hypothesize that oral poison uptake might be the reason why we did not find viable virus in the trophallactic fluid. The fifth chapter encompasses preliminary data on potential social immunization. However, our experiments do not confirm an actual survival benefit for the nestmates upon pathogen challenge under the given experimental settings. Nevertheless, we do not want to rule out the possibility for nestmate immunization, but rather emphasize that considering different experimental timelines and viral doses would provide a multitude of options for follow-up experiments. In conclusion, we find that prophylactic individual behaviors, such as oral poison uptake, might play a role in preventing viral disease transmission. Compared to colony defense against external pathogens, internal pathogen infections require a stronger component of individual physiological immunity than behavioral social immunity, yet could still lead to collective protection.

1-Lipschitz neural networks are more expressive with N-activations - Prach, Bernd; Lampert, Christoph (arXiv)
A crucial property for achieving secure, trustworthy and interpretable deep learning systems is their robustness: small changes to a system's inputs should not result in large changes to its outputs. Mathematically, this means one strives for networks with a small Lipschitz constant. Several recent works have focused on how to construct such Lipschitz networks, typically by imposing constraints on the weight matrices. In this work, we study an orthogonal aspect, namely the role of the activation function. We show that commonly used activation functions, such as MaxMin, as well as all piece-wise linear ones with two segments unnecessarily restrict the class of representable functions, even in the simplest one-dimensional setting. We furthermore introduce the new N-activation function that is provably more expressive than currently popular activation functions. We provide code at this https URL.

Data and code for: The genetic architecture of a recent transition to live-bearing in marine snails - Stankowski, Sean
This repository contains the code and VCF files needed to conduct the analyses in our MS. Each folder contains a readMe document explaining the nature of each file and dataset and the results and analyses that they relate to. The same anlaysis code (but not VCF files) is also available at https://github.com/seanstankowski/Littorina_reproductive_mode

Nitrate, auxin and cytokinin - a trio to tango - Abualia, R; Riegler, Stefan; Benková, Eva (Cells)
Nitrogen is an important macronutrient required for plant growth and development, thus directly impacting agricultural productivity. In recent years, numerous studies have shown that nitrogen-driven growth depends on pathways that control nitrate/nitrogen homeostasis and hormonal networks that act both locally and systemically to coordinate growth and development of plant organs. In this review, we will focus on recent advances in understanding the role of the plant hormones auxin and cytokinin and their crosstalk in nitrate-regulated growth and discuss the significance of novel findings and possible missing links.

Regulation of neural progenitor survival by Shh and BMP in the developing spinal cord - Kuzmicz-Kowalska, Katarzyna
Morphogens are signaling molecules that are known for their prominent role in pattern formation within developing tissues. In addition to patterning, morphogens also control tissue growth. However, the underlying mechanisms are poorly understood. We studied the role of morphogens in regulating tissue growth in the developing vertebrate neural tube. In this system, opposing morphogen gradients of Shh and BMP establish the dorsoventral pattern of neural progenitor domains. Perturbations in these morphogen pathways result in alterations in tissue growth and cell cycle progression, however, it has been unclear what cellular process is affected. To address this, we analysed the rates of cell proliferation and cell death in mouse mutants in which signaling is perturbed, as well as in chick neural plate explants exposed to defined concentrations of signaling activators or inhibitors. Our results indicated that the rate of cell proliferation was not altered in these assays. By contrast, both the Shh and BMP signaling pathways had profound effects on neural progenitor survival. Our results indicate that these pathways synergise to promote cell survival within neural progenitors. Consistent with this, we found that progenitors within the intermediate region of the neural tube, where the combined levels of Shh and BMP are the lowest, are most prone to cell death when signaling activity is inhibited. In addition, we found that downregulation of Shh results in increased apoptosis within the roof plate, which is the dorsal source of BMP ligand production. This revealed a cross-interaction between the Shh and BMP morphogen signaling pathways that may be relevant for understanding how gradients scale in neural tubes with different overall sizes. We further studied the mechanism acting downstream of Shh in cell survival regulation using genetic and genomic approaches. We propose that Shh transcriptionally regulates a non-canonical apoptotic pathway. Altogether, our study points to a novel role of opposing morphogen gradients in tissue size regulation and provides new insights into complex interactions between Shh and BMP signaling gradients in the neural tube.

Causality in the time of LLMs: Round table discussion results of CLeaR 2023 - Zhang, Cheng; Janzing, Dominik; van der Schaar, Mihaela; Locatello, Francesco; Spirtes, Peter; Zhang, Kun; Schölkopf, Bernhard; Uhler, Caroline (2nd Conference on Causal Learning and Reasoning)
The field of machine learning and AI has witnessed remarkable breakthroughs with the emergence of LLMs, which have also sparked a lively debate in the causal community. As researchers in this field, we are interested in exploring how LLMs relate to causality research, and how we can leverage the technology to advance it. In the second conference of Causal Learning and Reasoning (CLeaR), 2023, we held a round table discussion to gather and integrate the diverse perspectives of the CLeaR community on this topic. There is a general consensus that LLMs are not yet capable of causal reasoning at the current stage but has a lot of potential with public available information by CLeaR 2023. Enhancing causal machine learning is vital not only for its own sake but also to help LLMs improve their performance, especially regarding trustworthiness. In this document, we present both the summary and the raw outcome of the round table discussion. We acknowledge that with the progress of both fields, the opportunities and impact may rapidly change. We will repeat the same exercise in CLeaR 2024 to document the evolution.

Transition from tonic to phasic neurotransmitter release by presynaptic GABAB receptor activation in medial habenula terminals - Shigemoto, Ryuichi
GABAB receptor (GBR) activation inhibits neurotransmitter release in axon terminals in the brain, except in medial habenula (MHb) terminals, which show robust potentiation. However, mechanisms underlying this enigmatic potentiation remain elusive. Here, we report that GBR activation on MHb terminals induces an activity-dependent transition from a facilitating, tonic to a depressing, phasic neurotransmitter release mode. This transition is accompanied by a 4.1-fold increase in readily releasable vesicle pool (RRP) size and a 3.5-fold increase of docked synaptic vesicles at the presynaptic active zone (AZ). Strikingly, tonic and phasic release exhibit distinct coupling distances and are selectively affected by deletion of synaptoporin (SPO) and Ca2+-dependent activator protein for secretion 2 (CAPS2), respectively. SPO modulates augmentation, the short-term plasticity associated with tonic release, and CAPS2 retains the increased RRP for initial responses in phasic response trains. Double pre-embedding immunolabeling confirmed the co-localization of CAPS2 and SPO inside the same terminal. The cytosolic protein CAPS2 showed a synaptic vesicle (SV)-associated distribution similar to the vesicular transmembrane protein SPO. A newly developed “Flash and Freeze-fracture” method revealed the release of SPO-associated vesicles in both tonic and phasic modes and activity-dependent recruitment of CAPS2 to the AZ during phasic release, which lasted several minutes. Overall, these results indicate that GBR activation translocates CAPS2 to the AZ along with the fusion of CAPS2-associated SVs, contributing to a persistent RRP increase. Thus, we discovered structural and molecular mechanisms underlying tonic and phasic neurotransmitter release and their transition by GBR activation in MHb terminals.
Keywords: medial habenula; GABAB receptor; vesicle release; Flash and Freeze; Flash and Freeze-fracture

An observed population of intermediate-mass helium stars that have been stripped in binaries - Drout, M. R.; Götberg, Ylva Louise Linsdotter; Ludwig, B. A.; Groh, J. H.; de Mink, S. E.; O’Grady, A. J. G.; Smith, N. (Science)
The hydrogen-rich outer layers of massive stars can be removed by interactions with a binary companion. Theoretical models predict that this stripping produces a population of hot helium stars of ~2 to 8 solar masses (M☉), however, only one such system has been identified thus far. We used ultraviolet photometry to identify potential stripped helium stars then investigated 25 of them using optical spectroscopy. We identified stars with high temperatures (~60,000 to 100,000 kelvin), high surface gravities, and hydrogen-depleted surfaces; 16 stars also showed binary motion. These properties match expectations for stars with initial masses of 8 to 25 M☉ that were stripped by binary interaction. Their masses fall in the gap between subdwarf helium stars and Wolf-Rayet stars. We propose that these stars could be progenitors of stripped-envelope supernovae.
Keywords: Stellar Astrophysics

Multiplicative auction algorithm for approximate maximum weight bipartite matching - Zheng, Da Wei; Henzinger, Monika H (International Conference on Integer Programming and Combinatorial Optimization)
We present an auction algorithm using multiplicative instead of constant weight updates to compute a (1−ε)-approximate maximum weight matching (MWM) in a bipartite graph with n vertices and m edges in time O(mε−1log(ε−1)), matching the running time of the linear-time approximation algorithm of Duan and Pettie [JACM ’14]. Our algorithm is very simple and it can be extended to give a dynamic data structure that maintains a (1−ε)-approximate maximum weight matching under (1) one-sided vertex deletions (with incident edges) and (2) one-sided vertex insertions (with incident edges sorted by weight) to the other side. The total time time used is O(mε−1log(ε−1)), where m is the sum of the number of initially existing and inserted edges.

Geometric characterization of the persistence of 1D maps - Biswas, Ranita; Cultrera Di Montesano, Sebastiano; Edelsbrunner, Herbert; Saghafian, Morteza (Journal of Applied and Computational Topology)
We characterize critical points of 1-dimensional maps paired in persistent homology geometrically and this way get elementary proofs of theorems about the symmetry of persistence diagrams and the variation of such maps. In particular, we identify branching points and endpoints of networks as the sole source of asymmetry and relate the cycle basis in persistent homology with a version of the stable marriage problem. Our analysis provides the foundations of fast algorithms for maintaining a collection of sorted lists together with its persistence diagram.

Singlet oxygen in non-aqueous oxygen redox: Direct spectroscopic evidence for formation pathways and reliability of chemical probes - Mondal, Soumyadip; Jethwa, Rajesh B; Pant, Bhargavi; Hauschild, Robert; Freunberger, Stefan Alexander (Faraday Discussions)
Singlet oxygen (1O2) formation is now recognised as a key aspect of non-aqueous oxygen redox chemistry. For identifying 1O2, chemical trapping via 9,10-dimethylanthracene (DMA) to form the endoperoxide (DMA-O2) has become the mainstay method due to its sensitivity, selectivity, and ease of use. While DMA has been shown to be selective for 1O2, rather than forming DMA-O2 with a wide variety of potentially reactive O-containing species, false positives might hypothetically be obtained in the presence of previously overlooked species. Here, we first give unequivocal direct spectroscopic proof by the 1O2-specific near infrared (NIR) emission at 1270 nm for the previously proposed 1O2 formation pathways, which centre around superoxide disproportionation. We then show that peroxocarbonates, common intermediates in metal-O2 and metal carbonate electrochemistry, do not produce false-positive DMA-O2. Moreover, we identify a previously unreported 1O2-forming pathway through the reaction of CO2 with superoxide. Overall, we give unequivocal proof for 1O2 formation in non-aqueous oxygen redox and show that chemical trapping with DMA is a reliable method to assess 1O2 formation.
Keywords: Physical and Theoretical Chemistry

Weak-strong stability and phase-field approximation of interface evolution problems in fluid mechanics and in material sciences - Marveggio, Alice
This thesis concerns the application of variational methods to the study of evolution problems arising in fluid mechanics and in material sciences. The main focus is on weak-strong stability properties of some curvature driven interface evolution problems, such as the two-phase Navier–Stokes flow with surface tension and multiphase mean curvature flow, and on the phase-field approximation of the latter. Furthermore, we discuss a variational approach to the study of a class of doubly nonlinear wave equations. First, we consider the two-phase Navier–Stokes flow with surface tension within a bounded domain. The two fluids are immiscible and separated by a sharp interface, which intersects the boundary of the domain at a constant contact angle of ninety degree. We devise a suitable concept of varifolds solutions for the associated interface evolution problem and we establish a weak-strong uniqueness principle in case of a two dimensional ambient space. In order to focus on the boundary effects and on the singular geometry of the evolving domains, we work for simplicity in the regime of same viscosities for the two fluids. The core of the thesis consists in the rigorous proof of the convergence of the vectorial Allen-Cahn equation towards multiphase mean curvature flow for a suitable class of multi- well potentials and for well-prepared initial data. We even establish a rate of convergence. Our relative energy approach relies on the concept of gradient-flow calibration for branching singularities in multiphase mean curvature flow and thus enables us to overcome the limitations of other approaches. To the best of the author’s knowledge, our result is the first quantitative and unconditional one available in the literature for the vectorial/multiphase setting. This thesis also contains a first study of weak-strong stability for planar multiphase mean curvature flow beyond the singularity resulting from a topology change. Previous weak-strong results are indeed limited to time horizons before the first topology change of the strong solution. We consider circular topology changes and we prove weak-strong stability for BV solutions to planar multiphase mean curvature flow beyond the associated singular times by dynamically adapting the strong solutions to the weak one by means of a space-time shift. In the context of interface evolution problems, our proofs for the main results of this thesis are based on the relative energy technique, relying on novel suitable notions of relative energy functionals, which in particular measure the interface error. Our statements follow from the resulting stability estimates for the relative energy associated to the problem. At last, we introduce a variational approach to the study of nonlinear evolution problems. This approach hinges on the minimization of a parameter dependent family of convex functionals over entire trajectories, known as Weighted Inertia-Dissipation-Energy (WIDE) functionals. We consider a class of doubly nonlinear wave equations and establish the convergence, up to subsequences, of the associated WIDE minimizers to a solution of the target problem as the parameter goes to zero.

Concentration without independence via information measures - Esposito, Amedeo Roberto; Mondelli, Marco (Proceedings of 2023 IEEE International Symposium on Information Theory)
We propose a novel approach to concentration for non-independent random variables. The main idea is to ``pretend'' that the random variables are independent and pay a multiplicative price measuring how far they are from actually being independent. This price is encapsulated in the Hellinger integral between the joint and the product of the marginals, which is then upper bounded leveraging tensorisation properties. Our bounds represent a natural generalisation of concentration inequalities in the presence of dependence: we recover exactly the classical bounds (McDiarmid's inequality) when the random variables are independent. Furthermore, in a ``large deviations'' regime, we obtain the same decay in the probability as for the independent case, even when the random variables display non-trivial dependencies. To show this, we consider a number of applications of interest. First, we provide a bound for Markov chains with finite state space. Then, we consider the Simple Symmetric Random Walk, which is a non-contracting Markov chain, and a non-Markovian setting in which the stochastic process depends on its entire past. To conclude, we propose an application to Markov Chain Monte Carlo methods, where our approach leads to an improved lower bound on the minimum burn-in period required to reach a certain accuracy. In all of these settings, we provide a regime of parameters in which our bound fares better than what the state of the art can provide.

Enumerating matroids and linear spaces - Kwan, Matthew Alan; Sah, Ashwin; Sawhney, Mehtaab (Comptes Rendus Mathematique)
We show that the number of linear spaces on a set of n points and the number of rank-3 matroids on a ground set of size n are both of the form (cn+o(n))n2/6, where c=e3√/2−3(1+3–√)/2. This is the final piece of the puzzle for enumerating fixed-rank matroids at this level of accuracy: the numbers of rank-1 and rank-2 matroids on a ground set of size n have exact representations in terms of well-known combinatorial functions, and it was recently proved by van der Hofstad, Pendavingh, and van der Pol that for constant r≥4 there are (e1−rn+o(n))nr−1/r! rank-r matroids on a ground set of size n. In our proof, we introduce a new approach for bounding the number of clique decompositions of a complete graph, using quasirandomness instead of the so-called entropy method that is common in this area.

Maximal Lp-regularity and H∞-calculus for block operator matrices and applications - Agresti, Antonio; Hussein, Amru (Journal of Functional Analysis)
Many coupled evolution equations can be described via 2×2-block operator matrices of the form A=[ A B C D ] in a product space X=X1×X2 with possibly unbounded entries. Here, the case of diagonally dominant block operator matrices is considered, that is, the case where the full operator A can be seen as a relatively bounded perturbation of its diagonal part with D(A)=D(A)×D(D) though with possibly large relative bound. For such operators the properties of sectoriality, R-sectoriality and the boundedness of the H∞-calculus are studied, and for these properties perturbation results for possibly large but structured perturbations are derived. Thereby, the time dependent parabolic problem associated with A can be analyzed in maximal Lpt -regularity spaces, and this is applied to a wide range of problems such as different theories for liquid crystals, an artificial Stokes system, strongly damped wave and plate equations, and a Keller-Segel model.
Keywords: Analysis

Cooperation between bHLH transcription factors and histones for DNA access - Michael, Alicia; Stoos, Lisa; Crosby, Priya; Eggers, Nikolas; Nie, Xinyu Y.; Makasheva, Kristina; Minnich, Martina; Healy, Kelly L.; Weiss, Joscha; Kempf, Georg; Cavadini, Simone; Kater, Lukas; et al. (Nature)
The basic helix–loop–helix (bHLH) family of transcription factors recognizes DNA motifs known as E-boxes (CANNTG) and includes 108 members 1 . Here we investigate how chromatinized E-boxes are engaged by two structurally diverse bHLH proteins: the proto-oncogene MYC-MAX and the circadian transcription factor CLOCK-BMAL1 (refs. 2,3 ). Both transcription factors bind to E-boxes preferentially near the nucleosomal entry–exit sites. Structural studies with engineered or native nucleosome sequences show that MYC-MAX or CLOCK-BMAL1 triggers the release of DNA from histones to gain access. Atop the H2A–H2B acidic patch 4 , the CLOCK-BMAL1 Per-Arnt-Sim (PAS) dimerization domains engage the histone octamer disc. Binding of tandem E-boxes 5–7 at endogenous DNA sequences occurs through direct interactions between two CLOCK-BMAL1 protomers and histones and is important for circadian cycling. At internal E-boxes, the MYC-MAX leucine zipper can also interact with histones H2B and H3, and its binding is indirectly enhanced by OCT4 elsewhere on the nucleosome. The nucleosomal E-box position and the type of bHLH dimerization domain jointly determine the histone contact, the affinity and the degree of competition and cooperativity with other nucleosome-bound factors.

Readout of histone methylation by Trim24 locally restricts chromatin opening by p53 - Isbel, Luke; Iskar, Murat; Durdu, Sevi; Weiss, Joscha; Grand, Ralph S.; Hietter-Pfeiffer, Eric; Kozicka, Zuzanna; Michael, Alicia; Burger, Lukas; Thomä, Nicolas H.; Schübeler, Dirk (Nature Structural & Molecular Biology)
The genomic binding sites of the transcription factor (TF) and tumor suppressor p53 are unusually diverse with regard to their chromatin features, including histone modifications, raising the possibility that the local chromatin environment can contextualize p53 regulation. Here, we show that epigenetic characteristics of closed chromatin, such as DNA methylation, do not influence the binding of p53 across the genome. Instead, the ability of p53 to open chromatin and activate its target genes is locally restricted by its cofactor Trim24. Trim24 binds to both p53 and unmethylated histone 3 lysine 4 (H3K4), thereby preferentially localizing to those p53 sites that reside in closed chromatin, whereas it is deterred from accessible chromatin by H3K4 methylation. The presence of Trim24 increases cell viability upon stress and enables p53 to affect gene expression as a function of the local chromatin state. These findings link H3K4 methylation to p53 function and illustrate how specificity in chromatin can be achieved, not by TF-intrinsic sensitivity to histone modifications, but by employing chromatin-sensitive cofactors that locally modulate TF function.
Keywords: Molecular Biology; Structural Biology

Mesoscopic eigenvalue statistics for Wigner-type matrices - Riabov, Volodymyr (arXiv)
We prove a universal mesoscopic central limit theorem for linear eigenvalue statistics of a Wigner-type matrix inside the bulk of the spectrum with compactly supported twice continuously differentiable test functions. The main novel ingredient is an optimal local law for the two-point function $T(z,ζ)$ and a general class of related quantities involving two resolvents at nearby spectral parameters.

The detection of polarized X-ray emission from the magnetar 1E 2259+586 - Heyl, Jeremy; Taverna, Roberto; Turolla, Roberto; Israel, Gian Luca; Ng, Mason; Kırmızıbayrak, Demet; González-Caniulef, Denis; Caiazzo, Ilaria; Zane, Silvia; Ehlert, Steven R; Negro, Michela; Agudo, Iván; et al. (Monthly Notices of the Royal Astronomical Society)
We report on IXPE, NICER, and XMM–Newton observations of the magnetar 1E 2259+586. We find that the source is significantly polarized at about or above 20 per cent for all phases except for the secondary peak where it is more weakly polarized. The polarization degree is strongest during the primary minimum which is also the phase where an absorption feature has been identified previously. The polarization angle of the photons are consistent with a rotating vector model with a mode switch between the primary minimum and the rest of the rotation of the neutron star. We propose a scenario in which the emission at the source is weakly polarized (as in a condensed surface) and, as the radiation passes through a plasma arch, resonant cyclotron scattering off of protons produces the observed polarized radiation. This confirms the magnetar nature of the source with a surface field greater than about 1015 G.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Complex variations in X-ray polarization in the X-ray pulsar LS V +44 17/RX J0440.9+4431 - Doroshenko, Victor; Poutanen, Juri; Heyl, Jeremy; Tsygankov, Sergey S.; Caiazzo, Ilaria; Turolla, Roberto; Veledina, Alexandra; Weisskopf, Martin C.; Forsblom, Sofia V.; González-Caniulef, Denis; Loktev, Vladislav; Malacaria, Christian; et al. (Astronomy & Astrophysics)
We report on Imaging X-ray polarimetry explorer (IXPE) observations of the Be-transient X-ray pulsar LS V +44 17/RX J0440.9+4431 made at two luminosity levels during the giant outburst in January–February 2023. Considering the observed spectral variability and changes in the pulse profiles, the source was likely caught in supercritical and subcritical states with significantly different emission-region geometry, associated with the presence of accretion columns and hot spots, respectively. We focus here on the pulse-phase-resolved polarimetric analysis and find that the observed dependencies of the polarization degree and polarization angle (PA) on the pulse phase are indeed drastically different for the two observations. The observed differences, if interpreted within the framework of the rotating vector model (RVM), imply dramatic variations in the spin axis inclination, the position angle, and the magnetic colatitude by tens of degrees within the space of just a few days. We suggest that the apparent changes in the observed PA phase dependence are predominantly related to the presence of an unpulsed polarized component in addition to the polarized radiation associated with the pulsar itself. We then show that the observed PA phase dependence in both observations can be explained with a single set of RVM parameters defining the pulsar’s geometry. We also suggest that the additional polarized component is likely produced by scattering of the pulsar radiation in the equatorial disk wind.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Orbital decay in an accreting and eclipsing 13.7 minute orbital period binary with a luminous donor - Burdge, Kevin B.; El-Badry, Kareem; Rappaport, Saul; Sunny Wong, Tin Long; Bauer, Evan B.; Bildsten, Lars; Caiazzo, Ilaria; Chakrabarty, Deepto; Chickles, Emma; Graham, Matthew J.; Kara, Erin; Kulkarni, S. R.; et al. (The Astrophysical Journal Letters)
We report the discovery of ZTF J0127+5258, a compact mass-transferring binary with an orbital period of 13.7 minutes. The system contains a white dwarf accretor, which likely originated as a post–common envelope carbon–oxygen (CO) white dwarf, and a warm donor (Teff,donor = 16,400 ± 1000 K). The donor probably formed during a common envelope phase between the CO white dwarf and an evolving giant that left behind a helium star or white dwarf in a close orbit with the CO white dwarf. We measure gravitational wave–driven orbital inspiral with ∼51σ significance, which yields a joint constraint on the component masses and mass transfer rate. While the accretion disk in the system is dominated by ionized helium emission, the donor exhibits a mixture of hydrogen and helium absorption lines. Phase-resolved spectroscopy yields a donor radial velocity semiamplitude of 771 ± 27 km s−1, and high-speed photometry reveals that the system is eclipsing. We detect a Chandra X-ray counterpart with LX ∼ 3 × 1031 erg s−1. Depending on the mass transfer rate, the system will likely either evolve into a stably mass-transferring helium cataclysmic variable, merge to become an R CrB star, or explode as a Type Ia supernova in the next million years. We predict that the Laser Space Interferometer Antenna (LISA) will detect the source with a signal-to-noise ratio of 24 ± 6 after 4 yr of observations. The system is the first LISA-loud mass-transferring binary with an intrinsically luminous donor, a class of sources that provide the opportunity to leverage the synergy between optical and infrared time domain surveys, X-ray facilities, and gravitational-wave observatories to probe general relativity, accretion physics, and binary evolution.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

SRGeJ045359.9+622444: A 55 minute period eclipsing AM Canum Venaticorum star discovered from a joint SRG/eROSITA + ZTF search - Rodriguez, Antonio C.; Galiullin, Ilkham; Gilfanov, Marat; Kulkarni, Shrinivas R.; Khamitov, Irek; Bikmaev, Ilfan; van Roestel, Jan; Yungelson, Lev; El-Badry, Kareem; Sunayev, Rashid; Prince, Thomas A.; Buntov, Mikhail; et al. (The Astrophysical Journal)
AM Canum Venaticorum (AM CVn) systems are ultracompact binaries where a white dwarf accretes from a helium-rich degenerate or semidegenerate donor. Some AM CVn systems will be among the loudest sources of gravitational waves for the upcoming Laser Interferometer Space Antenna; yet the formation channel of AM CVns remains uncertain. We report the study and characterization of a new eclipsing AM CVn, SRGeJ045359.9+622444 (hereafter, SRGeJ0453), discovered from a joint Spektrum-Roentgen-Gamma (SRG) Extended Roentgen Survey with an Imaging Telescope Array (eROSITA) mission and Zwicky Transient Facility program to identify cataclysmic variables (CVs). We obtained optical photometry to confirm the eclipse of SRGeJ0453 and determine the orbital period to be . We constrain the binary parameters by modeling the high-speed photometry and radial-velocity curves and find Mdonor = 0.044 ± 0.024M⊙ and Rdonor = 0.078 ± 0.012R⊙. The X-ray spectrum is approximated by a power-law model with an unusually flat photon index of Γ ∼ 1 previously seen in magnetic CVs with SRG/eROSITA, but verifying that the magnetic nature of SRGeJ0453 requires further investigation. Optical spectroscopy suggests that the donor star of SRGeJ0453 could have initially been a He star or a He white dwarf. SRGeJ0453 is the ninth eclipsing AM CVn system published to date, and its lack of optical outbursts have made it elusive in previous surveys. The discovery of SRGeJ0453 using joint X-ray and optical surveys highlights the potential for discovering similar systems in the near future.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

A rotating white dwarf shows different compositions on its opposite faces - Caiazzo, Ilaria; Burdge, Kevin B.; Tremblay, Pier-Emmanuel; Fuller, James; Ferrario, Lilia; Gänsicke, Boris T.; Hermes, J. J.; Heyl, Jeremy; Kawka, Adela; Kulkarni, S. R.; Marsh, Thomas R.; Mróz, Przemek; et al. (Nature)
White dwarfs, the extremely dense remnants left behind by most stars after their death, are characterized by a mass comparable to that of the Sun compressed into the size of an Earth-like planet. In the resulting strong gravity, heavy elements sink towards the centre and the upper layer of the atmosphere contains only the lightest element present, usually hydrogen or helium1,2. Several mechanisms compete with gravitational settling to change a white dwarf’s surface composition as it cools3, and the fraction of white dwarfs with helium atmospheres is known to increase by a factor of about 2.5 below a temperature of about 30,000 kelvin4,5,6,7,8; therefore, some white dwarfs that appear to have hydrogen-dominated atmospheres above 30,000 kelvin are bound to transition to be helium-dominated as they cool below it. Here we report observations of ZTF J203349.8+322901.1, a transitioning white dwarf with two faces: one side of its atmosphere is dominated by hydrogen and the other one by helium. This peculiar nature is probably caused by the presence of a small magnetic field, which creates an inhomogeneity in temperature, pressure or mixing strength over the surface9,10,11. ZTF J203349.8+322901.1 might be the most extreme member of a class of magnetic, transitioning white dwarfs—together with GD 323 (ref. 12), a white dwarf that shows similar but much more subtle variations. This class of white dwarfs could help shed light on the physical mechanisms behind the spectral evolution of white dwarfs.

The origin of ultramassive white dwarfs: hints from Gaia EDR3 - Fleury, Leesa; Caiazzo, Ilaria; Heyl, Jeremy (Monthly Notices of the Royal Astronomical Society)
Gaia Data Release 2 revealed a population of ultramassive white dwarfs on the Q branch that are moving anomalously fast for a local disc population with their young photometric ages. As the velocity dispersion of stars in the local disc increases with age, a proposed explanation of these white dwarfs is that they experience a cooling delay that causes current cooling models to infer photometric ages much younger than their true ages. To explore this explanation, we investigate the kinematics of ultramassive white dwarfs within 200 pc of the Sun using the improved Gaia Early Data Release 3 observations. We analyse the transverse motions of 0.95–1.25 M⊙ white dwarfs, subdivided by mass and age, and determine the distributions of the three-dimensional components of the transverse velocities. The results are compared to expectations based on observed kinematics of local main-sequence stars. We find a population of photometrically young (∼0.5–1.5 Gyr) ultramassive (∼1.15–1.25 M⊙) white dwarfs for which the transverse velocity component in the direction of Galactic rotation is more dispersed than for local disc stars of any age; thus, it is too dispersed to be explained by any cooling delay in white dwarfs originating from the local disc. Furthermore, the dispersion ratio of the velocity components in the Galactic plane for this population is also inconsistent with a local disc origin. We discuss some possible explanations of this kinematically anomalous population, such as a halo origin or production through dynamical effects of stellar triple systems.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

An extremely massive white dwarf escaped from the Hyades star cluster - Miller, David R.; Caiazzo, Ilaria; Heyl, Jeremy; Richer, Harvey B.; El-Badry, Kareem; Rodriguez, Antonio C.; Vanderbosch, Zachary P.; van Roestel, Jan (The Astrophysical Journal Letters)
We searched the Gaia DR3 database for ultramassive white dwarfs with kinematics consistent with having escaped the nearby Hyades open cluster, identifying three such candidates. Two of these candidates have masses estimated from Gaia photometry of approximately 1.1 solar masses; their status as products of single-stellar evolution that have escaped the cluster was deemed too questionable for immediate follow-up analysis. The remaining candidate has an expected mass >1.3 solar masses, significantly reducing the probability of it being an interloper. Analysis of follow-up Gemini GMOS spectroscopy for this source reveals a nonmagnetized hydrogen atmosphere white dwarf with a mass and age consistent with having formed from a single star. Assuming a single-stellar-evolution formation channel, we estimate a 97.8% chance that the candidate is a true escapee from the Hyades. With a determined mass of 1.317 solar masses, this is potentially the most massive known single-evolution white dwarf and is by far the most massive with a strong association with an open cluster.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Keck and Gemini spectral characterization of Lucy mission fly-by target (152830) Dinkinesh - Bolin, B.T.; Noll, K.S.; Caiazzo, Ilaria; Fremling, C.; Binzel, R.P. (Icarus)
Recently, the inner main belt asteroid (152830) Dinkinesh was identified as an additional fly- by target for the Lucy mission. The heliocentric orbit and approximate absolute magnitude of Dinkinesh are known, but little additional information was available prior to its selection as a target. In particular, the lack of color spectrophotometry or spectra made it impossible to assign a spectral type to Dinkinesh from which its albedo could be estimated. We set out to remedy this knowledge gap by obtaining visible wavelength spectra with the Keck telescope on 2022 November 23 and with Gemini-South on 2022 December 27. The spectra measured with the Keck I/Low Resolution Imaging Spectrometer (LRIS) and the Gemini South/Gemini Multi-Object Spectrograph South (GMOS-S) are most similar to the average spectrum of S- and Sq-type asteroids. The most diagnostic feature is the ≈15 ± 1% silicate absorption feature at ≈0.9–1.0 μm. Small S- and Sq-type asteroids have moderately high albedos ranging from 0.17 to 0.35. Using this albedo range for Dinkinesh in combination with measured absolute magnitude, it is possible to derive an effective diameter and surface brightness for this body. The albedo, size and surface brightness are important inputs required for planning a successful encounter by the Lucy spacecraft.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Constraining axions with ZTF J1901+1458 - Fleury, Leesa; Caiazzo, Ilaria; Heyl, Jeremy (Physical Review D)
The axion-nucleon coupling enables the production of axions through the decay of excited 57Fe nuclei, and axions produced in the Sun through this process are often a target of helioscope searches. We show for the first time that hot, highly magnetic white dwarfs such as ZTF J1901+1458 are a viable target to search for the x-ray signature of axions that were produced by the 57Fe transition in the core and then converted to photons in the magnetosphere. We calculate that a 100 ks observation of ZTF J1901+1458 with NuSTAR would constrain the coupling of axions to nucleons and photons at a level below the bounds of both current and future planned helioscopes.

A strong x-ray polarization signal from the magnetar 1RXS J170849.0-400910 - Zane, Silvia; Taverna, Roberto; González–Caniulef, Denis; Muleri, Fabio; Turolla, Roberto; Heyl, Jeremy; Uchiyama, Keisuke; Ng, Mason; Tamagawa, Toru; Caiazzo, Ilaria; Di Lalla, Niccolò; Marshall, Herman L.; et al. (The Astrophysical Journal Letters)
Magnetars are the most strongly magnetized neutron stars, and one of the most promising targets for X-ray polarimetric measurements. We present here the first Imaging X-ray Polarimetry Explorer observation of the magnetar 1RXS J170849.0-400910, jointly analyzed with a new Swift observation and archival NICER data. The total (energy- and phase-integrated) emission in the 2–8 keV energy range is linerarly polarized, at a ∼35% level. The phase-averaged polarization signal shows a marked increase with energy, ranging from ∼20% at 2–3 keV up to ∼80% at 6–8 keV, while the polarization angle remains constant. This indicates that radiation is mostly polarized in a single direction. The spectrum is well reproduced by a combination of either two thermal (blackbody) components or a blackbody and a power law. Both the polarization degree and angle also show a variation with the spin phase, and the former is almost anticorrelated with the source counts in the 2–8 and 2–4 keV bands. We discuss the possible implications and interpretations, based on a joint analysis of the spectral, polarization, and pulsation properties of the source. A scenario in which the surface temperature is not homogeneous, with a hotter cap covered by a gaseous atmosphere and a warmer region in a condensed state, provides a satisfactory description of both the phase- and energy-dependent spectro-polarimetric data. The (comparatively) small size of the two emitting regions, required to explain the observed pulsations, does not allow to reach a robust conclusion about the presence of vacuum birefringence effects.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Discovery of two polars from a crossmatch of ZTF and the SRG/eFEDS x-ray catalog - Rodriguez, Antonio C.; Kulkarni, Shrinivas R.; Prince, Thomas A.; Szkody, Paula; Burdge, Kevin B.; Caiazzo, Ilaria; van Roestel, Jan; Vanderbosch, Zachary P.; El-Badry, Kareem; Bellm, Eric C.; Gänsicke, Boris T.; Graham, Matthew J.; et al. (The Astrophysical Journal)
Magnetic cataclysmic variables (CVs) are luminous Galactic X-ray sources, which have been difficult to find in purely optical surveys due to their lack of outburst behavior. The eROSITA telescope on board the Spektr-RG mission is conducting an all-sky X-ray survey and recently released the public eROSITA Final Equatorial Depth Survey (eFEDS) catalog. We crossmatched the eFEDS catalog with photometry from the Zwicky Transient Facility and discovered two new magnetic CVs. We obtained high-cadence optical photometry and phase-resolved spectroscopy for each magnetic CV candidate and found them both to be polars. Among the newly discovered magnetic CVs is eFEDS J085037.2+044359/ZTFJ0850+0443, an eclipsing polar with orbital period Porb = 1.72 hr and WD mass MWD = 0.81 ± 0.08M⊙. We suggest that eFEDS J085037.2+044359/ZTFJ0850+0443 is a low magnetic field strength polar, with BWD ≲ 10 MG. We also discovered a non-eclipsing polar, eFEDS J092614.1+010558/ZTFJ0926+0105, with orbital period Porb = 1.47 hr and magnetic field strength BWD = 36–42 MG.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Unbinned likelihood analysis for X-ray polarization - González-Caniulef, Denis; Caiazzo, Ilaria; Heyl, Jeremy (Monthly Notices of the Royal Astronomical Society)
We present a systematic study of the unbinned, photon-by-photon likelihood technique which can be used as an alternative method to analyse phase-dependent, X-ray spectro-polarimetric observations obtained with IXPE and other photoelectric polarimeters. We apply the unbinned technique to models of the luminous X-ray pulsar Hercules X-1, for which we produce simulated observations using the IXPEOBSSIM package. We consider minimal knowledge about the actual physical process responsible for the polarized emission from the accreting pulsar and assume that the observed phase-dependent polarization angle can be described by the rotating vector model. Using the unbinned technique, the detector’s modulation factor, and the polarization information alone, we found that both the rotating vector model and the underlying spectro-polarimetry model can reconstruct equally well the geometric configuration angles of the accreting pulsar. However, the measured polarization fraction becomes biased with respect to the underlying model unless the energy dispersion and effective area of the detector are also taken into account. To this end, we present an energy-dispersed likelihood estimator that is proved to be unbiased. For different analyses, we obtain posterior distributions from multiple IXPEOBSSIM realizations and show that the unbinned technique yields smaller error bars than the binned technique. We also discuss alternative sources, such as magnetars, in which the unbinned technique and the rotating vector model might be applied.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

IXPE simulations for magnetars - González-Caniulef, Denis; Caiazzo, Ilaria; Heyl, Jeremy (Proceedings of the International Astronomical Union)
Due to the rich phenomenology and extreme magnetic conditions, magnetars will be targets of great interest for the upcoming polarimetry space missions. In particular, the Imaging X-ray Polarimetry Explorer (IXPE), recently launched in December 2021, will operate in the 2–8 keV range. This will open a new window to study the polarized, persistent X-ray emission from magnetars. In this talk, I will present simulations of IXPE observations of magnetars using the IXPEObsSim package. I will discuss future prospect to discriminate between different magnetar’s emission mechanisms, as well as a potential detection of the signal of vacuum birefringence using IXPE.
Keywords: Astronomy and Astrophysics; Space and Planetary Science

X-ray polarization at the crossroads - Heyl, Jeremy; Caiazzo, Ilaria; González-Caniulef, Denis (Proceedings of the International Astronomical Union)
We argue that measurements of X-ray polarization using the recently launched Imaging X-ray Polarimetry Explorer will answer many open questions about magnetars in particular the physical state of their surfaces, whether vacuum birefringence exists, and the nature of the hard X-ray emission from these objects. We outline the capabilities of the instrument, specific models and the results of simulations for the magnetar 4U 0142+61.
Keywords: Astronomy and Astrophysics; Space and Planetary Science

Genetic load, eco-evolutionary feedback and extinction in a metapopulation - Olusanya, Oluwafunmilola O; Khudiakova, Kseniia; Sachdeva, Himani (bioRxiv)
Fragmented landscapes pose a significant threat to the persistence of species as they are highly susceptible to heightened risk of extinction due to the combined effects of genetic and demographic factors such as genetic drift and demographic stochasticity. This paper explores the intricate interplay between genetic load and extinction risk within metapopulations with a focus on understanding the impact of eco-evolutionary feedback mechanisms. We distinguish between two models of selection: soft selection, characterised by subpopulations maintaining carrying capacity despite load, and hard selection, where load can significantly affect population size. Within the soft selection framework, we investigate the impact of gene flow on genetic load at a single locus, while also considering the effect of selection strength and dominance coefficient. We subsequently build on this to examine how gene flow influences both population size and load under hard selection as well as identify critical thresholds for metapopulation persistence. Our analysis employs the diffusion, semi-deterministic and effective migration approximations. Our findings reveal that under soft selection, even modest levels of migration can significantly alleviate the burden of load. In sharp contrast, with hard selection, a much higher degree of gene flow is required to mitigate load and prevent the collapse of the metapopulation. Overall, this study sheds light into the crucial role migration plays in shaping the dynamics of genetic load and extinction risk in fragmented landscapes, offering valuable insights for conservation strategies and the preservation of diversity in a changing world.

Provably-efficient and internally-deterministic parallel Union-Find - Fedorov, Alexander; Hashemi, Diba; Nadiradze, Giorgi; Alistarh, Dan-Adrian (Proceedings of the 35th ACM Symposium on Parallelism in Algorithms and Architectures)
Determining the degree of inherent parallelism in classical sequential algorithms and leveraging it for fast parallel execution is a key topic in parallel computing, and detailed analyses are known for a wide range of classical algorithms. In this paper, we perform the first such analysis for the fundamental Union-Find problem, in which we are given a graph as a sequence of edges, and must maintain its connectivity structure under edge additions. We prove that classic sequential algorithms for this problem are well-parallelizable under reasonable assumptions, addressing a conjecture by [Blelloch, 2017]. More precisely, we show via a new potential argument that, under uniform random edge ordering, parallel union-find operations are unlikely to interfere: T concurrent threads processing the graph in parallel will encounter memory contention O(T2 · log |V| · log |E|) times in expectation, where |E| and |V| are the number of edges and nodes in the graph, respectively. We leverage this result to design a new parallel Union-Find algorithm that is both internally deterministic, i.e., its results are guaranteed to match those of a sequential execution, but also work-efficient and scalable, as long as the number of threads T is O(|E|1 over 3 - ε), for an arbitrarily small constant ε > 0, which holds for most large real-world graphs. We present lower bounds which show that our analysis is close to optimal, and experimental results suggesting that the performance cost of internal determinism is limited.

Gloss-aware color correction for 3D printing - Condor, Jorge; Piovarci, Michael; Bickel, Bernd; Didyk, Piotr (SIGGRAPH ’23 Conference Proceedings)
Color and gloss are fundamental aspects of surface appearance. State-of-the-art fabrication techniques can manipulate both properties of the printed 3D objects. However, in the context of appearance reproduction, perceptual aspects of color and gloss are usually handled separately, even though previous perceptual studies suggest their interaction. Our work is motivated by previous studies demonstrating a perceived color shift due to a change in the object's gloss, i.e., two samples with the same color but different surface gloss appear as they have different colors. In this paper, we conduct new experiments which support this observation and provide insights into the magnitude and direction of the perceived color change. We use the observations as guidance to design a new method that estimates and corrects the color shift enabling the fabrication of objects with the same perceived color but different surface gloss. We formulate the problem as an optimization procedure solved using differentiable rendering. We evaluate the effectiveness of our method in perceptual experiments with 3D objects fabricated using a multi-material 3D printer and demonstrate potential applications.
Keywords: color; gloss; perception; color compensation; color management

Runtime monitoring of dynamic fairness properties - Henzinger, Thomas A; Karimi, Mahyar; Kueffner, Konstantin; Mallik, Kaushik (FAccT '23: Proceedings of the 2023 ACM Conference on Fairness, Accountability, and Transparency)
A machine-learned system that is fair in static decision-making tasks may have biased societal impacts in the long-run. This may happen when the system interacts with humans and feedback patterns emerge, reinforcing old biases in the system and creating new biases. While existing works try to identify and mitigate long-run biases through smart system design, we introduce techniques for monitoring fairness in real time. Our goal is to build and deploy a monitor that will continuously observe a long sequence of events generated by the system in the wild, and will output, with each event, a verdict on how fair the system is at the current point in time. The advantages of monitoring are two-fold. Firstly, fairness is evaluated at run-time, which is important because unfair behaviors may not be eliminated a priori, at design-time, due to partial knowledge about the system and the environment, as well as uncertainties and dynamic changes in the system and the environment, such as the unpredictability of human behavior. Secondly, monitors are by design oblivious to how the monitored system is constructed, which makes them suitable to be used as trusted third-party fairness watchdogs. They function as computationally lightweight statistical estimators, and their correctness proofs rely on the rigorous analysis of the stochastic process that models the assumptions about the underlying dynamics of the system. We show, both in theory and experiments, how monitors can warn us (1) if a bank’s credit policy over time has created an unfair distribution of credit scores among the population, and (2) if a resource allocator’s allocation policy over time has made unfair allocations. Our experiments demonstrate that the monitors introduce very low overhead. We believe that runtime monitoring is an important and mathematically rigorous new addition to the fairness toolbox.

Whole-genome phylogeography of the intertidal snail Littorina saxatilis - Stankowski, Sean; Zagrodzka, Zuzanna B; Galindo, Juan; Montaño-Rendón, Mauricio; Faria, Rui; Mikhailova, Natalia; Blakeslee, April M H; Arnason, Einar; Broquet, Thomas; Morales, Hernán E; Grahame, John W; Westram, Anja M; et al. (Evolutionary Journal of the Linnean Society)
Understanding the factors that have shaped the current distributions and diversity of species is a central and longstanding aim of evolutionary biology. The recent inclusion of genomic data into phylogeographic studies has dramatically improved our understanding in organisms where evolutionary relationships have been challenging to infer. We used whole-genome sequences to study the phylogeography of the intertidal snail Littorina saxatilis, which has successfully colonized and diversified across a broad range of coastal environments in the Northern Hemisphere amid repeated cycles of glaciation. Building on past studies based on short DNA sequences, we used genome-wide data to provide a clearer picture of the relationships among samples spanning most of the species natural range. Our results confirm the trans-Atlantic colonization of North America from Europe, and have allowed us to identify rough locations of glacial refugia and to infer likely routes of colonization within Europe. We also investigated the signals in different datasets to account for the effects of genomic architecture and non-neutral evolution, which provides new insights about diversification of four ecotypes of L. saxatilis (the crab, wave, barnacle, and brackish ecotypes) at different spatial scales. Overall, we provide a much clearer picture of the biogeography of L. saxatilis, providing a foundation for more detailed phylogenomic and demographic studies.

The scorpionfly (Panorpa cognata) genome highlights conserved and derived features of the peculiar dipteran X chromosome - Lasne, Clementine; Elkrewi, Marwan N; Toups, Melissa A; Layana Franco, Lorena Alexandra; Macon, Ariana; Vicoso, Beatriz (Molecular Biology and Evolution)
Many insects carry an ancient X chromosome - the Drosophila Muller element F - that likely predates their origin. Interestingly, the X has undergone turnover in multiple fly species (Diptera) after being conserved for more than 450 MY. The long evolutionary distance between Diptera and other sequenced insect clades makes it difficult to infer what could have contributed to this sudden increase in rate of turnover. Here, we produce the first genome and transcriptome of a long overlooked sister-order to Diptera: Mecoptera. We compare the scorpionfly Panorpa cognata X-chromosome gene content, expression, and structure, to that of several dipteran species as well as more distantly-related insect orders (Orthoptera and Blattodea). We find high conservation of gene content between the mecopteran X and the dipteran Muller F element, as well as several shared biological features, such as the presence of dosage compensation and a low amount of genetic diversity, consistent with a low recombination rate. However, the two homologous X chromosomes differ strikingly in their size and number of genes they carry. Our results therefore support a common ancestry of the mecopteran and ancestral dipteran X chromosomes, and suggest that Muller element F shrank in size and gene content after the split of Diptera and Mecoptera, which may have contributed to its turnover in dipteran insects.
Keywords: Genetics; Molecular Biology; Ecology; Evolution; Behavior and Systematics

The scorpionfly (Panorpa cognata) genome highlights conserved and derived features of the peculiar dipteran X chromosome - Lasne, Clementine; Elkrewi, Marwan N
Many insects carry an ancient X chromosome—the Drosophila Muller element F—that likely predates their origin. Interestingly, the X has undergone turnover in multiple fly species (Diptera) after being conserved for more than 450 My. The long evolutionary distance between Diptera and other sequenced insect clades makes it difficult to infer what could have contributed to this sudden increase in rate of turnover. Here, we produce the first genome and transcriptome of scorpionflies (genus Panorpa), an insect belonging to a long overlooked sister-order to Diptera: Mecoptera. Combining our genome assembly with genomic short-read data, we obtain genome coverage and identify X-linked super-scaffolds. We further perform a gene homology analysis between the Panorpa X and a closely related Diptera species, and we assess the conservation of the Panorpa X-linked gene content with that of more distantly related insect species. We explored the structure of the Panorpa X by determining its repeat content, GC content, and nucleotide diversity. Finally, we used RNAseq data to detect the presence of dosage compensation in somatic tissues, as well as to explore gene expression tissue-specificity, and sex-bias in gene expression. We find high conservation of gene content between the mecopteran X and the dipteran Muller F element, as well as several shared biological features, such as the presence of dosage compensation and a low amount of genetic diversity, consistent with a low recombination rate. However, the 2 homologous X chromosomes differ strikingly in their size and number of genes they carry. Our results therefore support a common ancestry of the mecopteran and ancestral dipteran X chromosomes, and suggest that Muller element F shrank in size and gene content after the split of Diptera and Mecoptera, which may have contributed to its turnover in dipteran insects.
Keywords: Panorpa; scorpionfly; genome; transcriptome

Adaptive mutation in E. coli modulated by luxS - Hennessey-Wesen, Mike
Keywords: microfluidics; miceobiology; mutations; quorum sensing

Role of dynamin-related proteins 2 and SH3P2 in clathrin-mediated endocytosis in plants - Gnyliukh, Nataliia; Johnson, Alexander J; Nagel, Marie-Kristin; Monzer, Aline; Hlavata, Annamaria; Isono, Erika; Loose, Martin; Friml, Jiří (bioRxiv)
Clathrin-mediated endocytosis (CME) is vital for the regulation of plant growth and development by controlling plasma membrane protein composition and cargo uptake. CME relies on the precise recruitment of regulators for vesicle maturation and release. Homologues of components of mammalian vesicle scission are strong candidates to be part of the scissin machinery in plants, but the precise roles of these proteins in this process is not fully understood. Here, we characterised the roles of Plant Dynamin-Related Proteins 2 (DRP2s) and SH3-domain containing protein 2 (SH3P2), the plant homologue to Dynamins’ recruiters, like Endophilin and Amphiphysin, in the CME by combining high-resolution imaging of endocytic events in vivo and characterisation of the purified proteins in vitro. Although DRP2s and SH3P2 arrive similarly late during CME and physically interact, genetic analysis of the Dsh3p1,2,3 triple-mutant and complementation assays with non-SH3P2-interacting DRP2 variants suggests that SH3P2 does not directly recruit DRP2s to the site of endocytosis. These observations imply that despite the presence of many well-conserved endocytic components, plants have acquired a distinct mechanism for CME. One Sentence Summary In contrast to predictions based on mammalian systems, plant Dynamin-related proteins 2 are recruited to the site of Clathrin-mediated endocytosis independently of BAR-SH3 proteins.

Skin-Screen: A computational fabrication framework for color tattoos - Piovarci, Michael; Chapiro, Alexandre; Bickel, Bernd (ACM Transactions on Graphics)
Tattoos are a highly popular medium, with both artistic and medical applications. Although the mechanical process of tattoo application has evolved historically, the results are reliant on the artisanal skill of the artist. This can be especially challenging for some skin tones, or in cases where artists lack experience. We provide the first systematic overview of tattooing as a computational fabrication technique. We built an automated tattooing rig and a recipe for the creation of silicone sheets mimicking realistic skin tones, which allowed us to create an accurate model predicting tattoo appearance. This enables several exciting applications including tattoo previewing, color retargeting, novel ink spectra optimization, color-accurate prosthetics, and more.
Keywords: appearance; modeling; reproduction; tattoo; skin color; gamut mapping; ink-optimization; prosthetic

On lexicographic proof rules for probabilistic termination - Chatterjee, Krishnendu; Kafshdar Goharshady, Ehsan; Novotný, Petr; Zárevúcky, Jiří; Zikelic, Dorde (Formal Aspects of Computing)
We consider the almost-sure (a.s.) termination problem for probabilistic programs, which are a stochastic extension of classical imperative programs. Lexicographic ranking functions provide a sound and practical approach for termination of non-probabilistic programs, and their extension to probabilistic programs is achieved via lexicographic ranking supermartingales (LexRSMs). However, LexRSMs introduced in the previous work have a limitation that impedes their automation: all of their components have to be non-negative in all reachable states. This might result in a LexRSM not existing even for simple terminating programs. Our contributions are twofold. First, we introduce a generalization of LexRSMs that allows for some components to be negative. This standard feature of non-probabilistic termination proofs was hitherto not known to be sound in the probabilistic setting, as the soundness proof requires a careful analysis of the underlying stochastic process. Second, we present polynomial-time algorithms using our generalized LexRSMs for proving a.s. termination in broad classes of linear-arithmetic programs.
Keywords: Theoretical Computer Science; Software

Nanoparticle-based semiconductor solids: From synthesis to consolidation - Calcabrini, Mariano
High-performance semiconductors rely upon precise control of heat and charge transport. This can be achieved by precisely engineering defects in polycrystalline solids. There are multiple approaches to preparing such polycrystalline semiconductors, and the transformation of solution-processed colloidal nanoparticles is appealing because colloidal nanoparticles combine low cost with structural and compositional tunability along with rich surface chemistry. However, the multiple processes from nanoparticle synthesis to the final bulk nanocomposites are very complex. They involve nanoparticle purification, post-synthetic modifications, and finally consolidation (thermal treatments and densification). All these properties dictate the final material’s composition and microstructure, ultimately affecting its functional properties. This thesis explores the synthesis, surface chemistry and consolidation of colloidal semiconductor nanoparticles into dense solids. In particular, the transformations that take place during these processes, and their effect on the material’s transport properties are evaluated.

Professor Kerstin Johannesson–winner of the 2022 Molecular Ecology Prize - Westram, Anja M; Butlin, Roger (Molecular Ecology)
Kerstin Johannesson is a marine ecologist and evolutionary biologist based at the Tjärnö Marine Laboratory of the University of Gothenburg, which is situated in the beautiful Kosterhavet National Park on the Swedish west coast. Her work, using marine periwinkles (especially Littorina saxatilis and L. fabalis) as main model systems, has made a remarkable contribution to marine evolutionary biology and our understanding of local adaptation and its genetic underpinnings.
Keywords: Genetics; Ecology; Evolution; Behavior and Systematics

Ultrastructural characterization of natively preserved extracellular matrix by cryo-electron tomography - Zens, Bettina
The extracellular matrix (ECM) is a hydrated and complex three-dimensional network consisting of proteins, polysaccharides, and water. It provides structural scaffolding for the cells embedded within it and is essential in regulating numerous physiological processes, including cell migration and proliferation, wound healing, and stem cell fate. Despite extensive study, detailed structural knowledge of ECM components in physiologically relevant conditions is still rudimentary. This is due to methodological limitations in specimen preparation protocols which are incompatible with keeping large samples, such as the ECM, in their native state for subsequent imaging. Conventional electron microscopy (EM) techniques rely on fixation, dehydration, contrasting, and sectioning. This results in the alteration of a highly hydrated environment and the potential introduction of artifacts. Other structural biology techniques, such as nuclear magnetic resonance (NMR) spectroscopy and X-ray crystallography, allow high-resolution analysis of protein structures but only work on homogenous and purified samples, hence lacking contextual information. Currently, no approach exists for the ultrastructural and structural study of extracellular components under native conditions in a physiological, 3D environment. In this thesis, I have developed a workflow that allows for the ultrastructural analysis of the ECM in near-native conditions at molecular resolution. The developments I introduced include implementing a novel specimen preparation workflow for cell-derived matrices (CDMs) to render them compatible with ion-beam milling and subsequent high-resolution cryo-electron tomography (ET). To this end, I have established protocols to generate CDMs grown over several weeks on EM grids that are compatible with downstream cryo-EM sample preparation and imaging techniques. Characterization of these ECMs confirmed that they contain essential ECM components such as collagen I, collagen VI, and fibronectin I in high abundance and hence represent a bona fide biologically-relevant sample. I successfully optimized vitrification of these specimens by testing various vitrification techniques and cryoprotectants. In order to obtain high-resolution molecular insights into the ultrastructure and organization of CDMs, I established cryo-focused ion beam scanning electron microscopy (FIBSEM) on these challenging and complex specimens. I explored different approaches for the creation of thin cryo-lamellae by FIB milling and succeeded in optimizing the cryo-lift-out technique, resulting in high-quality lamellae of approximately 200 nm thickness. High-resolution Cryo-ET of these lamellae revealed for the first time the architecture of native CDM in the context of matrix-secreting cells. This allowed for the in situ visualization of fibrillar matrix proteins such as collagen, laying the foundation for future structural and ultrastructural characterization of these proteins in their near-native environment. In summary, in this thesis, I present a novel workflow that combines state-of-the-art cryo-EM specimen preparation and imaging technologies to permit characterization of the ECM, an important tissue component in higher organisms. This innovative and highly versatile workflow will enable addressing far-reaching questions on ECM architecture, composition, and reciprocal ECM-cell interactions.
Keywords: cryo-EM; cryo-ET; FIB milling; method development; FIBSEM; extracellular matrix; ECM; cell-derived matrices; CDMs; cell culture; high pressure freezing; HPF; structural biology; tomography; collagen

Mesendoderm formation in zebrafish gastrulation: The role of extraembryonic tissues - Schauer, Alexandra
The tight spatiotemporal coordination of signaling activity determining embryo patterning and the physical processes driving embryo morphogenesis renders embryonic development robust, such that key developmental processes can unfold relatively normally even outside of the full embryonic context. For instance, embryonic stem cell cultures can recapitulate the hallmarks of gastrulation, i.e. break symmetry leading to germ layer formation and morphogenesis, in a very reduced environment. This leads to questions on specific contributions of embryo-specific features, such as the presence of extraembryonic tissues, which are inherently involved in gastrulation in the full embryonic context. To address this, we established zebrafish embryonic explants without the extraembryonic yolk cell, an important player as a signaling source and for morphogenesis during gastrulation, as a model of ex vivo development. We found that dorsal-marginal determinants are required and sufficient in these explants to form and pattern all three germ layers. However, formation of tissues, which require the highest Nodal-signaling levels, is variable, demonstrating a contribution of extraembryonic tissues for reaching peak Nodal signaling levels. Blastoderm explants also undergo gastrulation-like axis elongation. We found that this elongation movement shows hallmarks of oriented mesendoderm cell intercalations typically associated with dorsal tissues in the intact embryo. These are disrupted by uniform upregulation of BMP signaling activity and concomitant explant ventralization, suggesting that tight spatial control of BMP signaling is a prerequisite for explant morphogenesis. This control is achieved by Nodal signaling, which is critical for effectively downregulating BMP signaling in the mesendoderm, highlighting that Nodal signaling is not only directly required for mesendoderm cell fate specification and morphogenesis, but also by maintaining low levels of BMP signaling at the dorsal side. Collectively, we provide insights into the capacity and organization of signaling and morphogenetic domains to recapitulate features of zebrafish gastrulation outside of the full embryonic context.

Plasticity in the cerebellum: What molecular mechanisms are behind physiological learning - Alcarva, Catarina
Understanding the mechanisms of learning and memory formation has always been one of the main goals in neuroscience. Already Pavlov (1927) in his early days has used his classic conditioning experiments to study the neural mechanisms governing behavioral adaptation. What was not known back then was that the part of the brain that is largely responsible for this type of associative learning is the cerebellum. Since then, plenty of theories on cerebellar learning have emerged. Despite their differences, one thing they all have in common is that learning relies on synaptic and intrinsic plasticity. The goal of my PhD project was to unravel the molecular mechanisms underlying synaptic plasticity in two synapses that have been shown to be implicated in motor learning, in an effort to understand how learning and memory formation are processed in the cerebellum. One of the earliest and most well-known cerebellar theories postulates that motor learning largely depends on long-term depression at the parallel fiber-Purkinje cell (PC-PC) synapse. However, the discovery of other types of plasticity in the cerebellar circuitry, like long-term potentiation (LTP) at the PC-PC synapse, potentiation of molecular layer interneurons (MLIs), and plasticity transfer from the cortex to the cerebellar/ vestibular nuclei has increased the popularity of the idea that multiple sites of plasticity might be involved in learning. Still a lot remains unknown about the molecular mechanisms responsible for these types of plasticity and whether they occur during physiological learning. In the first part of this thesis we have analyzed the variation and nanodistribution of voltagegated calcium channels (VGCCs) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid type glutamate receptors (AMPARs) on the parallel fiber-Purkinje cell synapse after vestibuloocular reflex phase reversal adaptation, a behavior that has been suggested to rely on PF-PC LTP. We have found that on the last day of adaptation there is no learning trace in form of VGCCs nor AMPARs variation at the PF-PC synapse, but instead a decrease in the number of PF-PC synapses. These data seem to support the view that learning is only stored in the cerebellar cortex in an initial learning phase, being transferred later to the vestibular nuclei. Next, we have studied the role of MLIs in motor learning using a relatively simple and well characterized behavioral paradigm – horizontal optokinetic reflex (HOKR) adaptation. We have found behavior-induced MLI potentiation in form of release probability increase that could be explained by the increase of VGCCs at the presynaptic side. Our results strengthen the idea of distributed cerebellar plasticity contributing to learning and provide a novel mechanism for release probability increase.

Structural and mechanistic study of bacterial complex I and its cyanobacterial ortholog - Kravchuk, Vladyslav
Most energy in humans is produced in form of ATP by the mitochondrial respiratory chain consisting of several protein assemblies embedded into lipid membrane (complexes I-V). Complex I is the first and the largest enzyme of the respiratory chain which is essential for energy production. It couples the transfer of two electrons from NADH to ubiquinone with proton translocation across bacterial or inner mitochondrial membrane. The coupling mechanism between electron transfer and proton translocation is one of the biggest enigma in bioenergetics and structural biology. Even though the enzyme has been studied for decades, only recent technological advances in cryo-EM allowed its extensive structural investigation. Complex I from E.coli appears to be of special importance because it is a perfect model system with a rich mutant library, however the structure of the entire complex was unknown. In this thesis I have resolved structures of the minimal complex I version from E. coli in different states including reduced, inhibited, under reaction turnover and several others. Extensive structural analyses of these structures and comparison to structures from other species allowed to derive general features of conformational dynamics and propose a universal coupling mechanism. The mechanism is straightforward, robust and consistent with decades of experimental data available for complex I from different species. Cyanobacterial NDH (cyanobacterial complex I) is a part of broad complex I superfamily and was studied as well in this thesis. It plays an important role in cyclic electron transfer (CET), during which electrons are cycled within PSI through ferredoxin and plastoquinone to generate proton gradient without NADPH production. Here, I solved structure of NDH and revealed additional state, which was not observed before. The novel “resting” state allowed to propose the mechanism of CET regulation. Moreover, conformational dynamics of NDH resembles one in complex I which suggest more broad universality of the proposed coupling mechanism. In summary, results presented here helped to interpret decades of experimental data for complex I and contributed to fundamental mechanistic understanding of protein function.

The nitrate transporter NRT2.1 directly antagonizes PIN7-mediated auxin transport for root growth adaptation - Wang, Yalu; Yuan, Zhi; Wang, Jinyi; Xiao, Huixin; Wan, Lu; Li, Lanxin; Guo, Yan; Gong, Zhizhong; Friml, Jiří; Zhang, Jing (Proceedings of the National Academy of Sciences of the United States of America)
As a crucial nitrogen source, nitrate (NO3−) is a key nutrient for plants. Accordingly, root systems adapt to maximize NO3− availability, a developmental regulation also involving the phytohormone auxin. Nonetheless, the molecular mechanisms underlying this regulation remain poorly understood. Here, we identify low-nitrate-resistant mutant (lonr) in Arabidopsis (Arabidopsis thaliana), whose root growth fails to adapt to low-NO3− conditions. lonr2 is defective in the high-affinity NO3− transporter NRT2.1. lonr2 (nrt2.1) mutants exhibit defects in polar auxin transport, and their low-NO3−-induced root phenotype depends on the PIN7 auxin exporter activity. NRT2.1 directly associates with PIN7 and antagonizes PIN7-mediated auxin efflux depending on NO3− levels. These results reveal a mechanism by which NRT2.1 in response to NO3− limitation directly regulates auxin transport activity and, thus, root growth. This adaptive mechanism contributes to the root developmental plasticity to help plants cope with changes in NO3− availability.

Generalizing medial axes with homology switches - Stephenson, Elizabeth R
We introduce the notion of a Faustian interchange in a 1-parameter family of smooth functions to generalize the medial axis to critical points of index larger than 0. We construct and implement a general purpose algorithm for approximating such generalized medial axes.

Panoramic functional gradients across the mouse retina - Kirillova, Kseniia
All visual experiences of the vertebrates begin with light being converted into electrical signals by the eye retina. Retinal ganglion cells (RGCs) are the neurons of the innermost layer of the mammal retina, and they transmit visual information to the rest of the brain. It has been shown that RGCs vary in their morphology and genetic profiles, moreover they can be unambiguously grouped into subtypes that share the same morphological and/or molecular properties. However, in terms of RGCs function, it remains unclear how many distinct types there are and what response properties their typology relies on. Even given the recent studies that successfully classified RGCs in a patch of the retina [1] and in scotopic conditions [2], the question remains whether the found subtypes persist across the entire retina. In this work, using a novel imaging method, we show that, when sampled from a large portion of the retina, RGCs can not be clearly divided into functional subtypes. We found that in photopic conditions, which implies more prominent natural scene statistic differences across the visual field, response properties can be exhibited by cells differently depending on their location in the retina, which leads to formation of a gradient of features rather than distinct classes. This finding suggests that RGCs follow a global organization across the visual field of the animal, adapting each RGC subtype to the requirements imposed by the natural scene statistics.

The effect of local population structure on genetic variation at selected loci in the A. majus hybrid zone - Julseth, Mara
The evolutionary processes that brought about today’s plethora of living species and the many billions more ancient ones all underlie biology. Evolutionary pathways are neither directed nor deterministic, but rather an interplay between selection, migration, mutation, genetic drift and other environmental factors. Hybrid zones, as natural crossing experiments, offer a great opportunity to use cline analysis to deduce different evolutionary processes - for example, selection strength. Theoretical cline models, largely assuming uniform distribution of individuals, often lack the capability of incorporating population structure. Since in reality organisms mostly live in patchy distributions and their dispersal is hardly ever Gaussian, it is necessary to unravel the effect of these different elements of population structure on cline parameters and shape. In this thesis, I develop a simulation inspired by the A. majus hybrid zone of a single selected locus under frequency dependent selection. This simulation enables us to untangle the effects of different elements of population structure as for example a low-density center and long-range dispersal. This thesis is therefore a first step towards theoretically untangling the effects of different elements of population structure on cline parameters and shape.

Mechanism of clathrin-coated vesicle formation during endocytosis in plants - Gnyliukh, Nataliia
Keywords: Clathrin-Mediated Endocytosis; vesicle scission; Dynamin-Related Protein 2; SH3P2; TPLATE complex; Total internal reflection fluorescence microscopy; Arabidopsis thaliana

Inverse shape design with parametric representations: Kirchhoff Rods and parametric surface models - Hafner, Christian
Inverse design problems in fabrication-aware shape optimization are typically solved on discrete representations such as polygonal meshes. This thesis argues that there are benefits to treating these problems in the same domain as human designers, namely, the parametric one. One reason is that discretizing a parametric model usually removes the capability of making further manual changes to the design, because the human intent is captured by the shape parameters. Beyond this, knowledge about a design problem can sometimes reveal a structure that is present in a smooth representation, but is fundamentally altered by discretizing. In this case, working in the parametric domain may even simplify the optimization task. We present two lines of research that explore both of these aspects of fabrication-aware shape optimization on parametric representations. The first project studies the design of plane elastic curves and Kirchhoff rods, which are common mathematical models for describing the deformation of thin elastic rods such as beams, ribbons, cables, and hair. Our main contribution is a characterization of all curved shapes that can be attained by bending and twisting elastic rods having a stiffness that is allowed to vary across the length. Elements like these can be manufactured using digital fabrication devices such as 3d printers and digital cutters, and have applications in free-form architecture and soft robotics. We show that the family of curved shapes that can be produced this way admits geometric description that is concise and computationally convenient. In the case of plane curves, the geometric description is intuitive enough to allow a designer to determine whether a curved shape is physically achievable by visual inspection alone. We also present shape optimization algorithms that convert a user-defined curve in the plane or in three dimensions into the geometry of an elastic rod that will naturally deform to follow this curve when its endpoints are attached to a support structure. Implemented in an interactive software design tool, the rod geometry is generated in real time as the user edits a curve and enables fast prototyping. The second project tackles the problem of general-purpose shape optimization on CAD models using a novel variant of the extended finite element method (XFEM). Our goal is the decoupling between the simulation mesh and the CAD model, so no geometry-dependent meshing or remeshing needs to be performed when the CAD parameters change during optimization. This is achieved by discretizing the embedding space of the CAD model, and using a new high-accuracy numerical integration method to enable XFEM on free-form elements bounded by the parametric surface patches of the model. Our simulation is differentiable from the CAD parameters to the simulation output, which enables us to use off-the-shelf gradient-based optimization procedures. The result is a method that fits seamlessly into the CAD workflow because it works on the same representation as the designer, enabling the alternation of manual editing and fabrication-aware optimization at will.

The design space of Kirchhoff rods - Hafner, Christian; Bickel, Bernd (ACM Transactions on Graphics)
The Kirchhoff rod model describes the bending and twisting of slender elastic rods in three dimensions, and has been widely studied to enable the prediction of how a rod will deform, given its geometry and boundary conditions. In this work, we study a number of inverse problems with the goal of computing the geometry of a straight rod that will automatically deform to match a curved target shape after attaching its endpoints to a support structure. Our solution lets us finely control the static equilibrium state of a rod by varying the cross-sectional profiles along its length. We also show that the set of physically realizable equilibrium states admits a concise geometric description in terms of linear line complexes, which leads to very efficient computational design algorithms. Implemented in an interactive software tool, they allow us to convert three-dimensional hand-drawn spline curves to elastic rods, and give feedback about the feasibility and practicality of a design in real time. We demonstrate the efficacy of our method by designing and manufacturing several physical prototypes with applications to interior design and soft robotics.
Keywords: Computer Graphics; Computational Design; Computational Geometry; Shape Modeling

A versatile toolbox for the comprehensive analysis of nervous tissue organization with light microscopy - Michalska, Julia M
The brain is an exceptionally sophisticated organ consisting of billions of cells and trillions of connections that orchestrate our cognition and behavior. To decode its complex connectivity, it is pivotal to disentangle its intricate architecture spanning from cm-sized circuits down to tens of nm-small synapses. To achieve this goal, I developed CATS – Comprehensive Analysis of nervous Tissue across Scales, a versatile toolbox for obtaining a holistic view of nervous tissue context with (superresolution) fluorescence microscopy. CATS combines comprehensive labeling of the extracellular space, that is compatible with chemical fixation, with information on molecular markers, superresolved data acquisition and machine-learning based data analysis for segmentation and synapse identification. I used CATS to analyze key features of nervous tissue connectivity, ranging from whole tissue architecture, neuronal in- and output-fields, down to synapse morphology. Focusing on the hippocampal circuitry, I quantified synaptic transmission properties of mossy fiber boutons and analyzed the connectivity pattern of dentate gyrus granule cells with CA3 pyramidal neurons. This shows that CATS is a viable tool to study hallmarks of neuronal connectivity with light microscopy.

Constraints on probing quantum coherence to infer gravitational entanglement - Hosten, Onur (Physical Review Research)
Finding a feasible scheme for testing the quantum mechanical nature of the gravitational interaction has been attracting an increasing level of attention. Gravity mediated entanglement generation so far appears to be the key ingredient for a potential experiment. In a recent proposal [D. Carney et al., PRX Quantum 2, 030330 (2021)] combining an atom interferometer with a low-frequency mechanical oscillator, a coherence revival test is proposed for verifying this entanglement generation. With measurements performed only on the atoms, this protocol bypasses the need for correlation measurements. Here, we explore formulations of such a protocol, and specifically find that in the envisioned regime of operation with high thermal excitation, semiclassical models, where there is no concept of entanglement, also give the same experimental signatures. We elucidate in a fully quantum mechanical calculation that entanglement is not the source of the revivals in the relevant parameter regime. We argue that, in its current form, the suggested test is only relevant if the oscillator is nearly in a pure quantum state, and in this regime the effects are too small to be measurable. We further discuss potential open ends. The results highlight the importance and subtleties of explicitly considering how the quantum case differs from the classical expectations when testing for the quantum mechanical nature of a physical system.

1H NMR chemical exchange techniques reveal local and global effects of oxidized cytosine derivatives - Dubini, Romeo C. A.; Korytiaková, Eva; Schinkel, Thea; Heinrichs, Pia; Carell, Thomas; Rovo, Petra (ACS Physical Chemistry Au)
5-Carboxycytosine (5caC) is a rare epigenetic modification found in nucleic acids of all domains of life. Despite its sparse genomic abundance, 5caC is presumed to play essential regulatory roles in transcription, maintenance and base-excision processes in DNA. In this work, we utilize nuclear magnetic resonance (NMR) spectroscopy to address the effects of 5caC incorporation into canonical DNA strands at multiple pH and temperature conditions. Our results demonstrate that 5caC has a pH-dependent global destabilizing and a base-pair mobility enhancing local impact on dsDNA, albeit without any detectable influence on the ground-state B-DNA structure. Measurement of hybridization thermodynamics and kinetics of 5caC-bearing DNA duplexes highlighted how acidic environment (pH 5.8 and 4.7) destabilizes the double-stranded structure by ∼10–20 kJ mol–1 at 37 °C when compared to the same sample at neutral pH. Protonation of 5caC results in a lower activation energy for the dissociation process and a higher barrier for annealing. Studies on conformational exchange on the microsecond time scale regime revealed a sharply localized base-pair motion involving exclusively the modified site and its immediate surroundings. By direct comparison with canonical and 5-formylcytosine (5fC)-edited strands, we were able to address the impact of the two most oxidized naturally occurring cytosine derivatives in the genome. These insights on 5caC’s subtle sensitivity to acidic pH contribute to the long-standing questions of its capacity as a substrate in base excision repair processes and its purpose as an independent, stable epigenetic mark.

Flavors of sequential information flow - Bartocci, Ezio; Ferrere, Thomas; Henzinger, Thomas A; Nickovic, Dejan; Da Costa, Ana Oliveira (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics))
We study the problem of specifying sequential information-flow properties of systems. Information-flow properties are hyperproperties, as they compare different traces of a system. Sequential information-flow properties can express changes, over time, in the information-flow constraints. For example, information-flow constraints during an initialization phase of a system may be different from information-flow constraints that are required during the operation phase. We formalize several variants of interpreting sequential information-flow constraints, which arise from different assumptions about what can be observed of the system. For this purpose, we introduce a first-order logic, called Hypertrace Logic, with both trace and time quantifiers for specifying linear-time hyperproperties. We prove that HyperLTL, which corresponds to a fragment of Hypertrace Logic with restricted quantifier prefixes, cannot specify the majority of the studied variants of sequential information flow, including all variants in which the transition between sequential phases (such as initialization and operation) happens asynchronously. Our results rely on new equivalences between sets of traces that cannot be distinguished by certain classes of formulas from Hypertrace Logic. This presents a new approach to proving inexpressiveness results for HyperLTL.

Non relativistic quantum field theory: Dynamics and irreversibility - Daguerre, L.; Torroba, G.; Medina Ramos, Raimel A; Solís, M. (Anales de la Asociacion Fisica Argentina)
studiamos aspectos de Teoría Cuántica de Campos a densidad finita usando técnicas y conceptos de información cuántica. Nos enfocamos en fermiones de Dirac masivos con potencial químico en 1+1 dimensiones espacio-temporales. Usando la entropía de entrelazamiento en un intervalo, construimos la función c entrópica que es finita. Esta función c no es monótona, e incorpora el entrelazamiento de largo alcance proveniente de la superficie de Fermi. Motivados por trabajos previos de modelos en la red, calculamos numéricamente las entropías de Renyi y encontramos oscilaciones de Friedel. Seguidamente, analizamos la información mutua como una medida de correlación entre diferentes regiones. Usando una expansión de distancia grande desarrollada por Cardy, argumentamos que la información mutua detecta las correlaciones inducidas por la superficie de Fermi todavía al orden dominante en la expansión. Finalmente, analizamos la entropía relativa y sus generalizaciones de Renyi para distinguir estados con diferente carga. Encontramos que estados en diferentes sectores de superselección dan origen a un comportamiento super-extensivo en la entropía relativa.

Alpha rhythm induces attenuation-amplification dynamics in neural activity cascades - Lombardi, Fabrizio; Herrmann, Hans J.; Parrino, Liborio; Plenz, Dietmar; Scarpetta, Silvia; Vaudano, Anna Elisabetta; de Arcangelis, Lucilla; Shriki, Oren (bioRxiv)
Rhythmical cortical activity has long been recognized as a pillar in the architecture of brain functions. Yet, the dynamic organization of its underlying neuronal population activity remains elusive. Here we uncover a unique organizational principle regulating collective neural dynamics associated with the alpha rhythm in the awake resting-state. We demonstrate that cascades of neural activity obey attenuation-amplification dynamics (AAD), with a transition from the attenuation regime—within alpha cycles—to the amplification regime—across a few alpha cycles—that correlates with the characteristic frequency of the alpha rhythm. We find that this short-term AAD is part of a large-scale, size-dependent temporal structure of neural cascades that obeys the Omori law: Following large cascades, smaller cascades occur at a rate that decays as a power-law of the time elapsed from such events—a long-term AAD regulating brain activity over the timescale of seconds. We show that such an organization corresponds to the "waxing and waning" of the alpha rhythm. Importantly, we observe that short- and long-term AAD are unique to the awake resting-state, being absent during NREM sleep. These results provide a quantitative, dynamical description of the so-far-qualitative notion of the "waxing and waning" phenomenon, and suggest the AAD as a key principle governing resting-state dynamics across timescales.

Impurity with a resonance in the vicinity of the Fermi energy - Maslov, Mikhail; Lemeshko, Mikhail; Volosniev, Artem (Physical Review Research)
We study an impurity with a resonance level whose position coincides with the Fermi energy of the surrounding Fermi gas. An impurity causes a rapid variation of the scattering phase shift for fermions at the Fermi surface, introducing a new characteristic length scale into the problem. We investigate manifestations of this length scale in the self-energy of the impurity and in the density of the bath. Our calculations reveal a model-independent deformation of the density of the Fermi gas, which is determined by the width of the resonance. To provide a broader picture, we investigate time evolution of the density in quench dynamics, and study the behavior of the system at finite temperatures. Finally, we briefly discuss implications of our findings for the Fermi-polaron problem.

Parameter inference for stochastic biochemical models from perturbation experiments parallelised at the single cell level - Davidović, Anđela; Chait, Remy P; Batt, Gregory; Ruess, Jakob (PLoS Computational Biology)
Understanding and characterising biochemical processes inside single cells requires experimental platforms that allow one to perturb and observe the dynamics of such processes as well as computational methods to build and parameterise models from the collected data. Recent progress with experimental platforms and optogenetics has made it possible to expose each cell in an experiment to an individualised input and automatically record cellular responses over days with fine time resolution. However, methods to infer parameters of stochastic kinetic models from single-cell longitudinal data have generally been developed under the assumption that experimental data is sparse and that responses of cells to at most a few different input perturbations can be observed. Here, we investigate and compare different approaches for calculating parameter likelihoods of single-cell longitudinal data based on approximations of the chemical master equation (CME) with a particular focus on coupling the linear noise approximation (LNA) or moment closure methods to a Kalman filter. We show that, as long as cells are measured sufficiently frequently, coupling the LNA to a Kalman filter allows one to accurately approximate likelihoods and to infer model parameters from data even in cases where the LNA provides poor approximations of the CME. Furthermore, the computational cost of filtering-based iterative likelihood evaluation scales advantageously in the number of measurement times and different input perturbations and is thus ideally suited for data obtained from modern experimental platforms. To demonstrate the practical usefulness of these results, we perform an experiment in which single cells, equipped with an optogenetic gene expression system, are exposed to various different light-input sequences and measured at several hundred time points and use parameter inference based on iterative likelihood evaluation to parameterise a stochastic model of the system.

Nuclear pore complex maintenance and implications for age-related diseases - Liu, Jinqiang; HETZER, Martin W (Trends in Cell Biology)
Nuclear pore complexes (NPCs) bridge the nucleus and the cytoplasm and are indispensable for crucial cellular activities, such as bidirectional molecular trafficking and gene transcription regulation. The discovery of long-lived proteins (LLPs) in NPCs from postmitotic cells raises the exciting possibility that the maintenance of NPC integrity might play an inherent role in lifelong cell function. Age-dependent deterioration of NPCs and loss of nuclear integrity have been linked to age-related decline in postmitotic cell function and degenerative diseases. In this review, we discuss our current understanding of NPC maintenance in proliferating and postmitotic cells, and how malfunction of nucleoporins (Nups) might contribute to the pathogenesis of various neurodegenerative and cardiovascular diseases.
Keywords: Cell Biology

Fast graphical population protocols - Alistarh, Dan-Adrian; Gelashvili, Rati; Rybicki, Joel (25th International Conference on Principles of Distributed Systems)
Let G be a graph on n nodes. In the stochastic population protocol model, a collection of n indistinguishable, resource-limited nodes collectively solve tasks via pairwise interactions. In each interaction, two randomly chosen neighbors first read each other’s states, and then update their local states. A rich line of research has established tight upper and lower bounds on the complexity of fundamental tasks, such as majority and leader election, in this model, when G is a clique. Specifically, in the clique, these tasks can be solved fast, i.e., in n polylog n pairwise interactions, with high probability, using at most polylog n states per node. In this work, we consider the more general setting where G is an arbitrary regular graph, and present a technique for simulating protocols designed for fully-connected networks in any connected regular graph. Our main result is a simulation that is efficient on many interesting graph families: roughly, the simulation overhead is polylogarithmic in the number of nodes, and quadratic in the conductance of the graph. As a sample application, we show that, in any regular graph with conductance φ, both leader election and exact majority can be solved in φ^{-2} ⋅ n polylog n pairwise interactions, with high probability, using at most φ^{-2} ⋅ polylog n states per node. This shows that there are fast and space-efficient population protocols for leader election and exact majority on graphs with good expansion properties. We believe our results will prove generally useful, as they allow efficient technology transfer between the well-mixed (clique) case, and the under-explored spatial setting.

Beyond distributed subgraph detection: Induced subgraphs, multicolored problems and graph parameters - Nikabadi, Amir; Korhonen, Janne (25th International Conference on Principles of Distributed Systems)
Subgraph detection has recently been one of the most studied problems in the CONGEST model of distributed computing. In this work, we study the distributed complexity of problems closely related to subgraph detection, mainly focusing on induced subgraph detection. The main line of this work presents lower bounds and parameterized algorithms w.r.t structural parameters of the input graph: - On general graphs, we give unconditional lower bounds for induced detection of cycles and patterns of treewidth 2 in CONGEST. Moreover, by adapting reductions from centralized parameterized complexity, we prove lower bounds in CONGEST for detecting patterns with a 4-clique, and for induced path detection conditional on the hardness of triangle detection in the congested clique. - On graphs of bounded degeneracy, we show that induced paths can be detected fast in CONGEST using techniques from parameterized algorithms, while detecting cycles and patterns of treewidth 2 is hard. - On graphs of bounded vertex cover number, we show that induced subgraph detection is easy in CONGEST for any pattern graph. More specifically, we adapt a centralized parameterized algorithm for a more general maximum common induced subgraph detection problem to the distributed setting. In addition to these induced subgraph detection results, we study various related problems in the CONGEST and congested clique models, including for multicolored versions of subgraph-detection-like problems.

Quantifying the probing and selection of microenvironmental pores by motile immune cells - Kroll, Janina; Ruiz-Fernandez, Mauricio J.A.; Braun, Malte B.; Merrin, Jack; Renkawitz, Jörg (Current Protocols)
Immune cells are constantly on the move through multicellular organisms to explore and respond to pathogens and other harmful insults. While moving, immune cells efficiently traverse microenvironments composed of tissue cells and extracellular fibers, which together form complex environments of various porosity, stiffness, topography, and chemical composition. In this protocol we describe experimental procedures to investigate immune cell migration through microenvironments of heterogeneous porosity. In particular, we describe micro-channels, micro-pillars, and collagen networks as cell migration paths with alternative pore size choices. Employing micro-channels or micro-pillars that divide at junctions into alternative paths with initially differentially sized pores allows us to precisely (1) measure the cellular translocation time through these porous path junctions, (2) quantify the cellular preference for individual pore sizes, and (3) image cellular components like the nucleus and the cytoskeleton. This reductionistic experimental setup thus can elucidate how immune cells perform decisions in complex microenvironments of various porosity like the interstitium. The setup further allows investigation of the underlying forces of cellular squeezing and the consequences of cellular deformation on the integrity of the cell and its organelles. As a complementary approach that does not require any micro-engineering expertise, we describe the usage of three-dimensional collagen networks with different pore sizes. Whereas we here focus on dendritic cells as a model for motile immune cells, the described protocols are versatile as they are also applicable for other immune cell types like neutrophils and non-immune cell types such as mesenchymal and cancer cells. In summary, we here describe protocols to identify the mechanisms and principles of cellular probing, decision making, and squeezing during cellular movement through microenvironments of heterogeneous porosity.

A cautionary tale: Burning the medial axis is unstable - Chambers, Erin; Fillmore, Christopher D; Stephenson, Elizabeth R; Wintraecken, Mathijs (38th International Symposium on Computational Geometry)
The medial axis of a set consists of the points in the ambient space without a unique closest point on the original set. Since its introduction, the medial axis has been used extensively in many applications as a method of computing a topologically equivalent skeleton. Unfortunately, one limiting factor in the use of the medial axis of a smooth manifold is that it is not necessarily topologically stable under small perturbations of the manifold. To counter these instabilities various prunings of the medial axis have been proposed. Here, we examine one type of pruning, called burning. Because of the good experimental results, it was hoped that the burning method of simplifying the medial axis would be stable. In this work we show a simple example that dashes such hopes based on Bing’s house with two rooms, demonstrating an isotopy of a shape where the medial axis goes from collapsible to non-collapsible.

Mean-field analysis of piecewise linear solutions for wide ReLU networks - Shevchenko, Aleksandr; Kungurtsev, Vyacheslav; Mondelli, Marco (Journal of Machine Learning Research)
Understanding the properties of neural networks trained via stochastic gradient descent (SGD) is at the heart of the theory of deep learning. In this work, we take a mean-field view, and consider a two-layer ReLU network trained via noisy-SGD for a univariate regularized regression problem. Our main result is that SGD with vanishingly small noise injected in the gradients is biased towards a simple solution: at convergence, the ReLU network implements a piecewise linear map of the inputs, and the number of “knot” points -- i.e., points where the tangent of the ReLU network estimator changes -- between two consecutive training inputs is at most three. In particular, as the number of neurons of the network grows, the SGD dynamics is captured by the solution of a gradient flow and, at convergence, the distribution of the weights approaches the unique minimizer of a related free energy, which has a Gibbs form. Our key technical contribution consists in the analysis of the estimator resulting from this minimizer: we show that its second derivative vanishes everywhere, except at some specific locations which represent the “knot” points. We also provide empirical evidence that knots at locations distinct from the data points might occur, as predicted by our theory.

Web and Wireless Geographical Information Systems
This book constitutes the refereed proceedings of the 18th International Symposium on Web and Wireless Geographical Information Systems, W2GIS 2022, held in Konstanz, Germany, in April 2022. The 7 full papers presented together with 6 short papers in the volume were carefully reviewed and selected from 16 submissions. The papers cover topics that range from mobile GIS and Location-Based Services to Spatial Information Retrieval and Wireless Sensor Networks.

The persistent homology of dual digital image constructions - Bleile, Bea; Garin, Adélie; Heiss, Teresa; Maggs, Kelly; Robins, Vanessa (Research in Computational Topology 2)
To compute the persistent homology of a grayscale digital image one needs to build a simplicial or cubical complex from it. For cubical complexes, the two commonly used constructions (corresponding to direct and indirect digital adjacencies) can give different results for the same image. The two constructions are almost dual to each other, and we use this relationship to extend and modify the cubical complexes to become dual filtered cell complexes. We derive a general relationship between the persistent homology of two dual filtered cell complexes, and also establish how various modifications to a filtered complex change the persistence diagram. Applying these results to images, we derive a method to transform the persistence diagram computed using one type of cubical complex into a persistence diagram for the other construction. This means software for computing persistent homology from images can now be easily adapted to produce results for either of the two cubical complex constructions without additional low-level code implementation.

From the prefect’s desk: Gerard van Swieten’s library correspondence - Chlebak, Clara A; Reid, Peter H. (Library and Information History)
This article investigates library-related documents written by Gerard van Swieten (1700–72) during his tenure as Library Prefect in the Imperial Library of Vienna (1745–72). Van Swieten’s time as Library Prefect is considered through a textual analysis. Handwritten letters were deconstructed in terms of their appearance, layout, and tone in order to mine them for meaning. Furthermore, the contents were examined for library matters such as censorship, catalogues, and collection development. The Imperial Court Library held a prominent role as a repository for rare and valuable works, later becoming the National Library of Austria. Gerard van Swieten’s work as a librarian tends to be overlooked, perhaps because he is better known as the private physician of Maria Theresia, as well as a medical reformer. Nevertheless, he was a hard-working chief librarian deeply involved in all aspects of librarianship. Van Swieten endorsed modern scientific works, which were otherwise banned officially by the censorship commission, for the use of scholars in the library, expanded the collection by acquiring books through his network of scholars and publishers, and reissued library catalogues. He also provided for the comfort of users in the library reading room, at a time when such considerations were unusual. In conclusion, a proposal is made that van Swieten viewed his role as librarian with some importance and pride.

Proteomic Analysis of C. Elegans Neurons Using TurboID-Based Proximity Labeling - Artan, Murat; de Bono, Mario (Behavioral Neurogenetics)
The proteomes of specialized structures, and the interactomes of proteins of interest, provide entry points to elucidate the functions of molecular machines. Here, we review a proximity-labeling strategy that uses the improved E. coli biotin ligase TurboID to characterize C. elegans protein complexes. Although the focus is on C. elegans neurons, the method is applicable regardless of cell type. We describe detailed extraction procedures that solubilize the bulk of C. elegans proteins and highlight the importance of tagging endogenous genes, to ensure physiological expression levels. We review issues associated with non-specific background noise and the importance of appropriate controls. As proof of principle, we review our analysis of the interactome of a presynaptic active zone protein, ELKS-1. Our aim is to provide a detailed protocol for TurboID-based proximity labeling in C. elegans and to highlight its potential and its limitations to characterize protein complexes and subcellular compartments in this animal.

The MUSE eXtremely Deep Field: Individual detections of Lyα haloes around rest-frame UV-selected galaxies at z ≃ 2.9–4.4 - Kusakabe, Haruka; Verhamme, Anne; Blaizot, Jérémy; Garel, Thibault; Wisotzki, Lutz; Leclercq, Floriane; Bacon, Roland; Schaye, Joop; Gallego, Sofia G.; Kerutt, Josephine; Matthee, Jorryt J; Maseda, Michael; et al. (Astronomy & Astrophysics)
Hydrogen Lyα haloes (LAHs) are commonly used as a tracer of the circumgalactic medium (CGM) at high redshifts. In this work, we aim to explore the existence of Lyα haloes around individual UV-selected galaxies, rather than around Lyα emitters (LAEs), at high redshifts. Our sample was continuum-selected with F775W ≤ 27.5, and spectroscopic redshifts were assigned or constrained for all the sources thanks to the deepest (100- to 140-h) existing Very Large Telescope (VLT)/Multi-Unit Spectroscopic Explorer (MUSE) data with adaptive optics. The final sample includes 21 galaxies that are purely F775W-magnitude selected within the redshift range z ≈ 2.9 − 4.4 and within a UV magnitude range −20 ≤ M1500 ≤ −18, thus avoiding any bias toward LAEs. We tested whether galaxy’s Lyα emission is significantly more extended than the MUSE PSF-convolved continuum component. We find 17 LAHs and four non-LAHs. We report the first individual detections of extended Lyα emission around non-LAEs. The Lyα halo fraction is thus as high as 81.0−11.2+10.3%, which is close to that for LAEs at z = 3 − 6 in the literature. This implies that UV-selected galaxies generally have a large amount of hydrogen in their CGM. We derived the mean surface brightness (SB) profile for our LAHs with cosmic dimming corrections and find that Lyα emission extends to 5.4 arcsec (≃40 physical kpc at the midpoint redshift z = 3.6) above the typical 1σ SB limit. The incidence rate of surrounding gas detected in Lyα per one-dimensional line of sight per unit redshift, dn/dz, is estimated to be 0.76−0.09+0.09 for galaxies with M1500 ≤ −18 mag at z ≃ 3.7. Assuming that Lyα emission and absorption arise in the same gas, this suggests, based on abundance matching, that LAHs trace the same gas as damped Lyα systems (DLAs) and sub-DLAs.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; galaxies: high-redshift / galaxies: formation / galaxies: evolution / cosmology: observations

Equivalent widths of Lyman α emitters in MUSE-Wide and MUSE-Deep - Kerutt, J.; Wisotzki, L.; Verhamme, A.; Schmidt, K. B.; Leclercq, F.; Herenz, E. C.; Urrutia, T.; Garel, T.; Hashimoto, T.; Maseda, M.; Matthee, Jorryt J; Kusakabe, H.; et al. (Astronomy & Astrophysics)
Context. The hydrogen Lyman α line is often the only measurable feature in optical spectra of high-redshift galaxies. Its shape and strength are influenced by radiative transfer processes and the properties of the underlying stellar population. High equivalent widths of several hundred Å are especially hard to explain by models and could point towards unusual stellar populations, for example with low metallicities, young stellar ages, and a top-heavy initial mass function. Other aspects influencing equivalent widths are the morphology of the galaxy and its gas properties. Aims. The aim of this study is to better understand the connection between the Lyman α rest-frame equivalent width (EW0) and spectral properties as well as ultraviolet (UV) continuum morphology by obtaining reliable EW0 histograms for a statistical sample of galaxies and by assessing the fraction of objects with large equivalent widths. Methods. We used integral field spectroscopy from the Multi Unit Spectroscopic Explorer (MUSE) combined with broad-band data from the Hubble Space Telescope (HST) to measure EW0. We analysed the emission lines of 1920 Lyman α emitters (LAEs) detected in the full MUSE-Wide (one hour exposure time) and MUSE-Deep (ten hour exposure time) surveys and found UV continuum counterparts in archival HST data. We fitted the UV continuum photometric images using the Galfit software to gain morphological information on the rest-UV emission and fitted the spectra obtained from MUSE to determine the double peak fraction, asymmetry, full-width at half maximum, and flux of the Lyman α line. Results. The two surveys show different histograms of Lyman α EW0. In MUSE-Wide, 20% of objects have EW0 > 240 Å, while this fraction is only 11% in MUSE-Deep and ≈16% for the full sample. This includes objects without HST continuum counterparts (one-third of our sample), for which we give lower limits for EW0. The object with the highest securely measured EW0 has EW0 = 589 ± 193 Å (the highest lower limit being EW0 = 4464 Å). We investigate the connection between EW0 and Lyman α spectral or UV continuum morphological properties. Conclusions. The survey depth has to be taken into account when studying EW0 distributions. We find that in general, high EW0 objects can have a wide range of spectral and UV morphological properties, which might reflect that the underlying causes for high EW0 values are equally varied.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; galaxies: high-redshift / galaxies: formation / galaxies: evolution / cosmology: observations

Deciphering stellar metallicities in the early universe: Case study of a young galaxy at z = 4.77 in the MUSE eXtremely Deep Field - Matthee, Jorryt J; Feltre, Anna; Maseda, Michael; Nanayakkara, Themiya; Boogaard, Leindert; Bacon, Roland; Verhamme, Anne; Leclercq, Floriane; Kusakabe, Haruka; Urrutia, Tanya; Wisotzki, Lutz (Astronomy & Astrophysics)
Directly characterising the first generations of stars in distant galaxies is a key quest of observational cosmology. We present a case study of ID53 at z = 4.77, the UV-brightest (but L⋆) star-forming galaxy at z > 3 in the MUSE eXtremely Deep Field with a mass of ≈109 M⊙. In addition to very strong Lyman-α (Lyα) emission, we clearly detect the (stellar) continuum and an N V P Cygni feature, interstellar absorption, fine-structure emission and nebular C IV emission lines in the 140 h spectrum. Continuum emission from two spatially resolved components in Hubble Space Telescope data are blended in the MUSE data, but we show that the nebular C IV emission originates from a subcomponent of the galaxy. The UV spectrum can be fit with recent BPASS stellar population models combined with single-burst or continuous star formation histories (SFHs), a standard initial mass function, and an attenuation law. Models with a young age and low metallicity (log10(age/yr) = 6.5–7.6 and [Z/H] = −2.15 to −1.15) are preferred, but the details depend on the assumed SFH. The intrinsic Hα luminosity of the best-fit models is an order of magnitude higher than the Hα luminosity inferred from Spitzer/IRAC data, which either suggests a high escape fraction of ionising photons, a high relative attenuation of nebular to stellar dust, or a complex SFH. The metallicity appears lower than the metallicity in more massive galaxies at z = 3 − 5, consistent with the scenario according to which younger galaxies have lower metallicities. This chemical immaturity likely facilitates Lyα escape, explaining why the Lyα equivalent width is anti-correlated with stellar metallicity. Finally, we stress that uncertainties in SFHs impose a challenge for future inferences of the stellar metallicity of young galaxies. This highlights the need for joint (spatially resolved) analyses of stellar spectra and photo-ionisation models.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; galaxies: high-redshift / techniques: spectroscopic / galaxies: stellar content / galaxies: formation

EMPRESS. IV. Extremely metal-poor galaxies including very low-mass primordial systems with M∗= 10⁴-10⁵⊙ and 2%–3% (O/H): High (Fe/O) suggestive of metal enrichment by hypernovae/pair-instability supernovae - Isobe, Yuki; Ouchi, Masami; Suzuki, Akihiro; Moriya, Takashi J.; Nakajima, Kimihiko; Nomoto, Ken’ichi; Rauch, Michael; Harikane, Yuichi; Kojima, Takashi; Ono, Yoshiaki; Fujimoto, Seiji; Inoue, Akio K.; et al. (The Astrophysical Journal)
We present Keck/LRIS follow-up spectroscopy for 13 photometric candidates of extremely metal-poor galaxies (EMPGs) selected by a machine-learning technique applied to the deep (∼26 AB mag) optical and wide-area (∼500 deg2) Subaru imaging data in the EMPRESS survey. Nine out of the 13 candidates are EMPGs with an oxygen abundance (O/H) less than ∼10% solar value (O/H)⊙, and four sources are contaminants of moderately metal-rich galaxies or no emission-line objects. Notably, two out of the nine EMPGs have extremely low stellar masses and oxygen abundances of 5 × 10⁴x–7 × -10⁵ M⊙ and 2%–3% (O/H)⊙, respectively. With a sample of five EMPGs with (Fe/O) measurements, two (three) of which are taken from this study (the literature), we confirm that two EMPGs with the lowest (O/H) ratios of ∼2% (O/H)⊙ show high (Fe/O) ratios of ∼0.1, close to the solar abundance ratio. Comparing galaxy chemical enrichment models, we find that the two EMPGs cannot be explained by a scenario of metal-poor gas accretion/episodic star formation history due to their low (N/O) ratios. We conclude that the two EMPGs can be reproduced by the inclusion of bright hypernovae and/or hypothetical pair-instability supernovae (SNe) preferentially produced in a metal-poor environment. This conclusion implies that primordial galaxies at z ∼ 10 could have a high abundance of Fe that did not originate from Type Ia SNe with delays and that Fe may not serve as a cosmic clock for primordial galaxies.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

The LEGA-C of nature and nurture in stellar populations at z ∼ 0.6–1.0: Dn4000 and Hδ reveal different assembly histories for quiescent galaxies in different environments - Sobral, David; van der Wel, Arjen; Bezanson, Rachel; Bell, Eric; Muzzin, Adam; D’Eugenio, Francesco; Darvish, Behnam; Gallazzi, Anna; Wu, Po-Feng; Maseda, Michael; Matthee, Jorryt J; Paulino-Afonso, Ana; et al. (The Astrophysical Journal)
Galaxy evolution is driven by a variety of physical processes that are predicted to proceed at different rates for different dark matter haloes and environments across cosmic times. A record of this evolution is preserved in galaxy stellar populations, which we can access using absorption-line spectroscopy. Here we explore the large LEGA-C survey (DR3) to investigate the role of the environment and stellar mass on stellar populations at z ∼ 0.6–1 in the COSMOS field. Leveraging the statistical power and depth of LEGA-C, we reveal significant gradients in Dn4000 and Hδ equivalent widths (EWs) distributions over the stellar mass versus environment 2D spaces for the massive galaxy population (M > 1010 M⊙) at z ∼ 0.6–1.0. Dn4000 and Hδ EWs primarily depend on stellar mass, but they also depend on environment at fixed stellar mass. By splitting the sample into centrals and satellites, and in terms of star-forming galaxies and quiescent galaxies, we reveal that the significant environmental trends of Dn4000 and Hδ EW, when controlling for stellar mass, are driven by quiescent galaxies. Regardless of being centrals or satellites, star-forming galaxies reveal Dn4000 and Hδ EWs, which depend strongly on their stellar mass and are completely independent of the environment at 0.6 < z < 1.0. The environmental trends seen for satellite galaxies are fully driven by the trends that hold only for quiescent galaxies, combined with the strong environmental dependency of the quiescent fraction at fixed stellar mass. Our results are consistent with recent predictions from simulations that point toward massive galaxies forming first in overdensities or the most compact dark matter haloes.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

On the variation in stellar α-enhancements of star-forming galaxies in the EAGLE simulation - Gebek, Andrea; Matthee, Jorryt J (The Astrophysical Journal)
The ratio of α-elements to iron in galaxies holds valuable information about the star formation history (SFH) since their enrichment occurs on different timescales. The fossil record of stars in galaxies has mostly been excavated for passive galaxies, since the light of star-forming galaxies is dominated by young stars, which have much weaker atmospheric absorption features. Here we use the largest reference cosmological simulation of the EAGLE project to investigate the origin of variations in stellar α-enhancement among star-forming galaxies at z = 0, and their impact on integrated spectra. The definition of α-enhancement in a composite stellar population is ambiguous. We elucidate two definitions—termed “mean” and “galactic” α-enhancement—in more detail. While a star-forming galaxy has a high “mean” α-enhancement when its stars formed rapidly, a galaxy with a large “galactic” α-enhancement generally had a delayed SFH. We find that absorption-line strengths of Mg and Fe correlate with variations in α-enhancement. These correlations are strongest for the “galactic” α-enhancement. However, we show that these are mostly caused by other effects that are cross-correlated with α-enhancement, such as variations in the light-weighted age. This severely complicates the retrieval of α-enhancements in star-forming galaxies. The ambiguity is not severe for passive galaxies, and we confirm that spectral variations in these galaxies are caused by measurable variations in α-enhancements. We suggest that this more complex coupling between α-enhancement and SFHs can guide the interpretation of new observations of star-forming galaxies.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

(Re)Solving reionization with Lyα: How bright Lyα emitters account for the z ≈ 2 − 8 cosmic ionizing background - Matthee, Jorryt J; Naidu, Rohan P.; Pezzulli, Gabriele; Gronke, Max; Sobral, David; Oesch, Pascal A.; Hayes, Matthew; Erb, Dawn; Schaerer, Daniel; Amorín, Ricardo; Tacchella, Sandro; Ana Paulino-Afonso, Ana Paulino-Afonso; et al. (Monthly Notices of the Royal Astronomical Society)
The cosmic ionizing emissivity from star-forming galaxies has long been anchored to UV luminosity functions. Here, we introduce an emissivity framework based on Lyα emitters (LAEs), which naturally hones in on the subset of galaxies responsible for the ionizing background due to the intimate connection between production and escape of Lyα and LyC photons. Using constraints on the escape fractions of bright LAEs (LLyα > 0.2L*) at z ≈ 2 obtained from resolved Lyα profiles, and arguing for their redshift-invariance, we show that: (i) quasars and LAEs together reproduce the relatively flat emissivity at z ≈ 2–6, which is non-trivial given the strong evolution in both the star formation density and quasar number density at these epochs and (ii) LAEs produce late and rapid reionization between z ≈ 6−9 under plausible assumptions. Within this framework, the >10 × rise in the UV population-averaged fesc between z ≈ 3–7 naturally arises due to the same phenomena that drive the growing LAE fraction with redshift. Generally, a LAE dominated emissivity yields a peak in the distribution of the ionizing budget with UV luminosity as reported in latest simulations. Using our adopted parameters (⁠fesc=50 per cent⁠, ξion = 1025.9 Hz erg−1 for half the bright LAEs), a highly ionizing minority of galaxies with MUV < −17 accounts for the entire ionizing budget from star-forming galaxies. Rapid flashes of LyC from such rare galaxies produce a ‘disco’ ionizing background. We conclude proposing tests to further develop our suggested Lyα-anchored formalism.
Keywords: galaxies: high-redshift; intergalactic medium; cosmology: observations; dark ages; reionization; first stars; ultraviolet: galaxies

The dynamics of complex box mappings - Clark, Trevor; Drach, Kostiantyn; Kozlovski, Oleg; Strien, Sebastian Van (Arnold Mathematical Journal)
In holomorphic dynamics, complex box mappings arise as first return maps to wellchosen domains. They are a generalization of polynomial-like mapping, where the domain of the return map can have infinitely many components. They turned out to be extremely useful in tackling diverse problems. The purpose of this paper is: • To illustrate some pathologies that can occur when a complex box mapping is not induced by a globally defined map and when its domain has infinitely many components, and to give conditions to avoid these issues. • To show that once one has a box mapping for a rational map, these conditions can be assumed to hold in a very natural setting. Thus, we call such complex box mappings dynamically natural. Having such box mappings is the first step in tackling many problems in one-dimensional dynamics. • Many results in holomorphic dynamics rely on an interplay between combinatorial and analytic techniques. In this setting, some of these tools are: • the Enhanced Nest (a nest of puzzle pieces around critical points) from Kozlovski, Shen, van Strien (AnnMath 165:749–841, 2007), referred to below as KSS; • the Covering Lemma (which controls the moduli of pullbacks of annuli) from Kahn and Lyubich (Ann Math 169(2):561–593, 2009); • the QC-Criterion and the Spreading Principle from KSS. The purpose of this paper is to make these tools more accessible so that they can be used as a ‘black box’, so one does not have to redo the proofs in new settings. • To give an intuitive, but also rather detailed, outline of the proof from KSS and Kozlovski and van Strien (Proc Lond Math Soc (3) 99:275–296, 2009) of the following results for non-renormalizable dynamically natural complex box mappings: • puzzle pieces shrink to points, • (under some assumptions) topologically conjugate non-renormalizable polynomials and box mappings are quasiconformally conjugate. • We prove the fundamental ergodic properties for dynamically natural box mappings. This leads to some necessary conditions for when such a box mapping supports a measurable invariant line field on its filled Julia set. These mappings are the analogues of Lattès maps in this setting. • We prove a version of Mañé’s Theorem for complex box mappings concerning expansion along orbits of points that avoid a neighborhood of the set of critical points.

The K2 Galactic Archaeology Program data release 3: Age-abundance patterns in C1–C8 and C10–C18 - Zinn, Joel C.; Stello, Dennis; Elsworth, Yvonne; García, Rafael A.; Kallinger, Thomas; Mathur, Savita; Mosser, Benoît; Hon, Marc; Bugnet, Lisa Annabelle; Jones, Caitlin; Reyes, Claudia; Sharma, Sanjib; et al. (The Astrophysical Journal)
We present the third and final data release of the K2 Galactic Archaeology Program (K2 GAP) for Campaigns C1–C8 and C10–C18. We provide asteroseismic radius and mass coefficients, κR and κM, for ∼19,000 red giant stars, which translate directly to radius and mass given a temperature. As such, K2 GAP DR3 represents the largest asteroseismic sample in the literature to date. K2 GAP DR3 stellar parameters are calibrated to be on an absolute parallactic scale based on Gaia DR2, with red giant branch and red clump evolutionary state classifications provided via a machine-learning approach. Combining these stellar parameters with GALAH DR3 spectroscopy, we determine asteroseismic ages with precisions of ∼20%–30% and compare age-abundance relations to Galactic chemical evolution models among both low- and high-α populations for α, light, iron-peak, and neutron-capture elements. We confirm recent indications in the literature of both increased Ba production at late Galactic times as well as significant contributions to r-process enrichment from prompt sources associated with, e.g., core-collapse supernovae. With an eye toward other Galactic archeology applications, we characterize K2 GAP DR3 uncertainties and completeness using injection tests, suggesting that K2 GAP DR3 is largely unbiased in mass/age, with uncertainties of 2.9% (stat.) ± 0.1% (syst.) and 6.7% (stat.) ± 0.3% (syst.) in κR and κM for red giant branch stars and 4.7% (stat.) ± 0.3% (syst.) and 11% (stat.) ± 0.9% (syst.) for red clump stars. We also identify percent-level asteroseismic systematics, which are likely related to the time baseline of the underlying data, and which therefore should be considered in TESS asteroseismic analysis.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Detections of solar-like oscillations in dwarfs and subgiants with Kepler DR25 short-cadence data - Mathur, S.; García, R. A.; Breton, S.; Santos, A. R. G.; Mosser, B.; Huber, D.; Sayeed, M.; Bugnet, Lisa Annabelle; Chontos, A. (Astronomy & Astrophysics)
During the survey phase of the Kepler mission, several thousand stars were observed in short cadence, allowing for the detection of solar-like oscillations in more than 500 main-sequence and subgiant stars. These detections showed the power of asteroseismology in determining fundamental stellar parameters. However, the Kepler Science Office discovered an issue in the calibration that affected half of the store of short-cadence data, leading to a new data release (DR25) with corrections on the light curves. In this work, we re-analyzed the one-month time series of the Kepler survey phase to search for solar-like oscillations that might have been missed when using the previous data release. We studied the seismic parameters of 99 stars, among which there are 46 targets with new reported solar-like oscillations, increasing, by around 8%, the known sample of solar-like stars with an asteroseismic analysis of the short-cadence data from this mission. The majority of these stars have mid- to high-resolution spectroscopy publicly available with the LAMOST and APOGEE surveys, respectively, as well as precise Gaia parallaxes. We computed the masses and radii using seismic scaling relations and we find that this new sample features massive stars (above 1.2 M⊙ and up to 2 M⊙) and subgiants. We determined the granulation parameters and amplitude of the modes, which agree with the scaling relations derived for dwarfs and subgiants. The stars studied here are slightly fainter than the previously known sample of main-sequence and subgiants with asteroseismic detections. We also studied the surface rotation and magnetic activity levels of those stars. Our sample of 99 stars has similar levels of activity compared to the previously known sample and is in the same range as the Sun between the minimum and maximum of its activity cycle. We find that for seven stars, a possible blend could be the reason for the non-detection with the early data release. Finally, we compared the radii obtained from the scaling relations with the Gaia ones and we find that the Gaia radii are overestimated by 4.4%, on average, compared to the seismic radii, with a scatter of 12.3% and a decreasing trend according to the evolutionary stage. In addition, for homogeneity purposes, we re-analyzed the DR25 of the main-sequence and subgiant stars with solar-like oscillations that were previously detected and, as a result, we provide the global seismic parameters for a total of 525 stars.
Keywords: Space and Planetary Science; Astronomy and Astrophysics

Hidden currents at the Sun’s surface - Bugnet, Lisa Annabelle (Nature Astronomy)
The Sun’s surface hosts varying magnetic activities and rotation rates (from equator to pole), and unique solar weather. Now, a combination of ground and space observations has unveiled a previously undetected magnetized plasma current.
Keywords: Astronomy and Astrophysics

Detecting deep axisymmetric toroidal magnetic fields in stars: The traditional approximation of rotation for differentially rotating deep spherical shells with a general azimuthal magnetic field - Dhouib, H.; Mathis, S.; Bugnet, Lisa Annabelle; Van Reeth, T.; Aerts, C. (Astronomy & Astrophysics)
Context. Asteroseismology has revealed small core-to-surface rotation contrasts in stars in the whole Hertzsprung–Russell diagram. This is the signature of strong transport of angular momentum (AM) in stellar interiors. One of the plausible candidates to efficiently carry AM is magnetic fields with various topologies that could be present in stellar radiative zones. Among them, strong axisymmetric azimuthal (toroidal) magnetic fields have received a lot of interest. Indeed, if they are subject to the so-called Tayler instability, the accompanying triggered Maxwell stresses can transport AM efficiently. In addition, the electromotive force induced by the fluctuations of magnetic and velocity fields could potentially sustain a dynamo action that leads to the regeneration of the initial strong axisymmetric azimuthal magnetic field. Aims. The key question we aim to answer is whether we can detect signatures of these deep strong azimuthal magnetic fields. The only way to answer this question is asteroseismology, and the best laboratories of study are intermediate-mass and massive stars with external radiative envelopes. Most of these are rapid rotators during their main sequence. Therefore, we have to study stellar pulsations propagating in stably stratified, rotating, and potentially strongly magnetised radiative zones, namely magneto-gravito-inertial (MGI) waves. Methods. We generalise the traditional approximation of rotation (TAR) by simultaneously taking general axisymmetric differential rotation and azimuthal magnetic fields into account. Both the Coriolis acceleration and the Lorentz force are therefore treated in a non-perturbative way. Using this new formalism, we derive the asymptotic properties of MGI waves and their period spacings. Results. We find that toroidal magnetic fields induce a shift in the period spacings of gravity (g) and Rossby (r) modes. An equatorial azimuthal magnetic field with an amplitude of the order of 105 G leads to signatures that are detectable in period spacings for high-radial-order g and r modes in γ Doradus (γ Dor) and slowly pulsating B (SPB) stars. More complex hemispheric configurations are more difficult to observe, particularly when they are localised out of the propagation region of MGI modes, which can be localised in an equatorial belt. Conclusions. The magnetic TAR, which takes into account toroidal magnetic fields in a non-perturbative way, is derived. This new formalism allows us to assess the effects of the magnetic field in γ Dor and SPB stars on g and r modes. We find that these effects should be detectable for equatorial fields thanks to modern space photometry using observations from Kepler, TESS CVZ, and PLATO.
Keywords: Space and Planetary Science; Astronomy and Astrophysics; magnetohydrodynamics (MHD) / waves / stars; rotation / stars: magnetic field / stars; oscillations / methods

Inferring couplings in networks across order-disorder phase transitions - Ngampruetikorn, Vudtiwat; Sachdeva, Vedant; Torrence, Johanna; Humplik, Jan; Schwab, David J.; Palmer, Stephanie E. (Physical Review Research)
Statistical inference is central to many scientific endeavors, yet how it works remains unresolved. Answering this requires a quantitative understanding of the intrinsic interplay between statistical models, inference methods, and the structure in the data. To this end, we characterize the efficacy of direct coupling analysis (DCA)—a highly successful method for analyzing amino acid sequence data—in inferring pairwise interactions from samples of ferromagnetic Ising models on random graphs. Our approach allows for physically motivated exploration of qualitatively distinct data regimes separated by phase transitions. We show that inference quality depends strongly on the nature of data-generating distributions: optimal accuracy occurs at an intermediate temperature where the detrimental effects from macroscopic order and thermal noise are minimal. Importantly our results indicate that DCA does not always outperform its local-statistics-based predecessors; while DCA excels at low temperatures, it becomes inferior to simple correlation thresholding at virtually all temperatures when data are limited. Our findings offer insights into the regime in which DCA operates so successfully, and more broadly, how inference interacts with the structure in the data.

Constant-time Dynamic (Δ +1)-Coloring - Henzinger, Monika H; Peng, Pan (ACM Transactions on Algorithms)
We give a fully dynamic (Las-Vegas style) algorithm with constant expected amortized time per update that maintains a proper (Δ +1)-vertex coloring of a graph with maximum degree at most Δ. This improves upon the previous O(log Δ)-time algorithm by Bhattacharya et al. (SODA 2018). Our algorithm uses an approach based on assigning random ranks to vertices and does not need to maintain a hierarchical graph decomposition. We show that our result does not only have optimal running time but is also optimal in the sense that already deciding whether a Δ-coloring exists in a dynamically changing graph with maximum degree at most Δ takes Ω (log n) time per operation.

The "New Synthesis" - Barton, Nicholas H (Proceedings of the National Academy of Sciences of the United States of America)
When Mendel’s work was rediscovered in 1900, and extended to establish classical genetics, it was initially seen in opposition to Darwin’s theory of evolution by natural selection on continuous variation, as represented by the biometric research program that was the foundation of quantitative genetics. As Fisher, Haldane, and Wright established a century ago, Mendelian inheritance is exactly what is needed for natural selection to work efficiently. Yet, the synthesis remains unfinished. We do not understand why sexual reproduction and a fair meiosis predominate in eukaryotes, or how far these are responsible for their diversity and complexity. Moreover, although quantitative geneticists have long known that adaptive variation is highly polygenic, and that this is essential for efficient selection, this is only now becoming appreciated by molecular biologists—and we still do not have a good framework for understanding polygenic variation or diffuse function.

Quantifying heterologous gene expression during ectopic MazF production in Escherichia coli - Nikolic, Nela; Sauert, Martina; Albanese, Tanino G.; Moll, Isabella (BMC Research Notes)
Objective: MazF is a sequence-specific endoribonuclease-toxin of the MazEF toxin–antitoxin system. MazF cleaves single-stranded ribonucleic acid (RNA) regions at adenine–cytosine–adenine (ACA) sequences in the bacterium Escherichia coli. The MazEF system has been used in various biotechnology and synthetic biology applications. In this study, we infer how ectopic mazF overexpression affects production of heterologous proteins. To this end, we quantified the levels of fluorescent proteins expressed in E. coli from reporters translated from the ACA-containing or ACA-less messenger RNAs (mRNAs). Additionally, we addressed the impact of the 5′-untranslated region of these reporter mRNAs under the same conditions by comparing expression from mRNAs that comprise (canonical mRNA) or lack this region (leaderless mRNA). Results: Flow cytometry analysis indicates that during mazF overexpression, fluorescent proteins are translated from the canonical as well as leaderless mRNAs. Our analysis further indicates that longer mazF overexpression generally increases the concentration of fluorescent proteins translated from ACA-less mRNAs, however it also substantially increases bacterial population heterogeneity. Finally, our results suggest that the strength and duration of mazF overexpression should be optimized for each experimental setup, to maximize the heterologous protein production and minimize the amount of phenotypic heterogeneity in bacterial populations, which is unfavorable in biotechnological processes.
Keywords: General Biochemistry; Genetics and Molecular Biology; General Medicine

Fully dynamic four-vertex subgraph counting - Hanauer, Kathrin; Henzinger, Monika H; Hua, Qi Cheng (1st Symposium on Algorithmic Foundations of Dynamic Networks)
This paper presents a comprehensive study of algorithms for maintaining the number of all connected four-vertex subgraphs in a dynamic graph. Specifically, our algorithms maintain the number of paths of length three in deterministic amortized O(m^{1/2}) update time, and any other connected four-vertex subgraph which is not a clique in deterministic amortized update time O(m^{2/3}). Queries can be answered in constant time. We also study the query times for subgraphs containing an arbitrary edge that is supplied only with the query as well as the case where only subgraphs containing a vertex s that is fixed beforehand are considered. For length-3 paths, paws, 4-cycles, and diamonds our bounds match or are not far from (conditional) lower bounds: Based on the OMv conjecture we show that any dynamic algorithm that detects the existence of paws, diamonds, or 4-cycles or that counts length-3 paths takes update time Ω(m^{1/2-δ}). Additionally, for 4-cliques and all connected induced subgraphs, we show a lower bound of Ω(m^{1-δ}) for any small constant δ > 0 for the amortized update time, assuming the static combinatorial 4-clique conjecture holds. This shows that the O(m) algorithm by Eppstein et al. [David Eppstein et al., 2012] for these subgraphs cannot be improved by a polynomial factor.

Recent advances in fully dynamic graph algorithms - Hanauer, Kathrin; Henzinger, Monika H; Schulz, Christian (1st Symposium on Algorithmic Foundations of Dynamic Networks)
In recent years, significant advances have been made in the design and analysis of fully dynamic algorithms. However, these theoretical results have received very little attention from the practical perspective. Few of the algorithms are implemented and tested on real datasets, and their practical potential is far from understood. Here, we present a quick reference guide to recent engineering and theory results in the area of fully dynamic graph algorithms.

Kac regularity and domination of quadratic forms - Wirth, Melchior (Advances in Operator Theory)
A domain is called Kac regular for a quadratic form on L2 if every functions vanishing almost everywhere outside the domain can be approximated in form norm by functions with compact support in the domain. It is shown that this notion is stable under domination of quadratic forms. As applications measure perturbations of quasi-regular Dirichlet forms, Cheeger energies on metric measure spaces and Schrödinger operators on manifolds are studied. Along the way a characterization of the Sobolev space with Dirichlet boundary conditions on domains in infinitesimally Riemannian metric measure spaces is obtained.
Keywords: Algebra and Number Theory; Analysis